Silicon-containing arylamine polymer, and electroluminescent device material and electroluminescent device using said polymer

A silicon-containing arylamine polymer addresses the band offset issues in QLEDs by enhancing triplet energy levels and reducing driving voltage, improving luminous efficiency and device durability.

JP7602318B2Active Publication Date: 2024-12-18SAMSUNG ELECTRONICS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2019127058
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-12-28
Filing Date
2019-07-08
Publication Date
2024-12-18
Estimated Expiration
2039-07-08

AI Technical Summary

Technical Problem

Conventional organic light-emitting diodes (OLEDs) and quantum dot electroluminescent devices (QLEDs) face challenges in efficient carrier injection due to significant band offset differences, leading to high driving voltages and reduced efficiency, with few known hole transport materials having the required HOMO levels.

Method used

A silicon-containing arylamine polymer with a specific structural unit is developed, which can be used as a hole transport layer material, enhancing triplet energy levels and reducing driving voltage, thereby improving luminous efficiency and charge mobility.

Benefits of technology

The silicon-containing arylamine polymer achieves high luminous efficiency with lower driving voltage, supports large-area device fabrication, and extends device lifetime by reducing electron deterioration, making it suitable for QLEDs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602318000063
    Figure 0007602318000063
  • Figure 0007602318000001
    Figure 0007602318000001
  • Figure 0007602318000002
    Figure 0007602318000002
Patent Text Reader

Abstract

To provide a technique that can improve luminous efficacy of an electroluminescent element.SOLUTION: An arylamine polymer including silicon, and having a structural unit (A) represented by Formula (1).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to silicon-containing arylamine polymers, and electroluminescent device materials and electroluminescent devices using the polymers. [Background technology]

[0002] Research and development of electroluminescence elements (EL elements) is being actively carried out. In particular, EL elements are considered to be promising for use as inexpensive solid-state light-emitting large-area full-color display elements and writing light source arrays. EL elements are light-emitting elements having a thin film of an organic material with a thickness of several nanometers to several hundred nanometers between an anode and a cathode. EL elements usually further have a hole transport layer, a light-emitting layer, an electron transport layer, and the like.

[0003] Of these, the light-emitting layer can be made of fluorescent or phosphorescent materials. Phosphorescent materials are expected to have about four times the luminous efficiency of fluorescent materials. In addition, to cover a wide color gamut, RGB light sources are required to have a narrow emission spectrum with a half-width. In particular, deep blue is required for blue, but currently no element has been found that satisfies the requirements for long life and color purity.

[0004] As a method for solving these problems, there is a light-emitting device that uses "quantum dots," an inorganic light-emitting material, as a light-emitting material (Patent Document 1). Quantum dots are semiconductor materials with a crystal structure of several nanometers in size, and are composed of hundreds to thousands of atoms. Quantum dots have a large surface area per unit volume because they are very small in size. Therefore, most of the atoms are present on the surface of the nanocrystals, and they exhibit quantum confinement effects. Due to this quantum confinement effect, quantum dots can adjust the emission wavelength simply by adjusting their size, and have characteristics such as excellent color purity and high PL (photoluminescence) luminous efficiency, so they have attracted much attention. A quantum dot electroluminescence device (QLED) is known as a basic element of a three-layer structure including a quantum dot light-emitting layer in between, a hole transport layer (HTL) and an electron transport layer (ETL) at both ends. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2010-199067 A Summary of the Invention [Problem to be solved by the invention]

[0006] Conventional organic light emitting diodes (OLEDs) include a hole transport layer (HTL) and an emission layer. The HOMO (Highest Occupied Molecular Orbital) level of the material used in the hole transport layer (HTL) is 5.0 to 5.3 eV. Also, the HOMO level of the material used in the emission layer is between 5.0 and 5.5 eV, so that the difference with the HOMO level of the material used in the hole transport layer (HTL) is small, allowing efficient hole transport, and providing a highly efficient device.

[0007] Meanwhile, the valance band level of quantum dots used in QLEDs is about 6.8 eV. This results in a large difference in band offset with the HOMO level of hole transport layer materials used in existing organic electroluminescent devices (OLEDs), resulting in problems such as reduced turn-on voltage, driving voltage, efficiency, and carrier injection efficiency of QLEDs. To solve these problems, methods are being considered to adjust the HOMO level of the hole transport layer (HTL) or to lower the band offset with the quantum dot (QD) layer by using an appropriate hole transport layer material. However, there are few hole transport materials with a HOMO level of 5.4 eV or higher (especially over 5.55 eV).

[0008] The present invention has been made in view of the above circumstances, and there is a demand for a material that can be used for the hole transport layer of a quantum dot electroluminescence element. In addition, in view of the recent competition in the development of light-emitting devices, there is a demand for light-emitting devices with higher luminous efficiency.

[0009] Therefore, the present invention has been made in consideration of the above circumstances, and has an object to provide a technique capable of improving the luminous efficiency of an electroluminescence element (particularly even a quantum dot electroluminescence element). [Means for solving the problem]

[0010] The present inventors have conducted extensive research to solve the above problems, and as a result have found that the above problems can be solved by using a polymer having a specific structure, thereby completing the present invention.

[0011] That is, the above object can be achieved by a silicon-containing arylamine polymer having a structural unit (A) represented by the following formula (1).

[0012] [ka]

[0013] However, Ar 1 each independently represents a substituted or unsubstituted aromatic hydrocarbon group having 6 to 25 carbon atoms or a substituted or unsubstituted heterocyclic aromatic group having 12 to 25 carbon atoms; Ar 2 represents a substituted or unsubstituted divalent aromatic hydrocarbon group having 6 to 25 carbon atoms or a substituted or unsubstituted divalent heterocyclic aromatic group having 12 to 25 carbon atoms; R 1 each independently represents a hydrogen atom, a linear, branched or cyclic hydrocarbon group having from 1 to 12 carbon atoms, or a substituted or unsubstituted aromatic hydrocarbon group having from 6 to 25 carbon atoms. [Brief description of the drawings]

[0014] [Figure 1] 1 is a schematic diagram showing an organic electroluminescence element according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] In a first aspect, the present invention provides a silicon-containing arylamine polymer having a constitutional unit (A) represented by the following formula (1):

[0016] [ka]

[0017] However, Ar 1 each independently represents a substituted or unsubstituted (optionally substituted) aromatic hydrocarbon group having from 6 to 25 carbon atoms or a substituted or unsubstituted (optionally substituted) heterocyclic aromatic group having from 12 to 25 carbon atoms; Ar 2 represents a substituted or unsubstituted (optionally substituted) divalent aromatic hydrocarbon group having 6 to 25 carbon atoms or a substituted or unsubstituted (optionally substituted) divalent heterocyclic aromatic group having 12 to 25 carbon atoms; R 1 each independently represents a hydrogen atom, a linear, branched or cyclic hydrocarbon group having from 1 to 12 carbon atoms, or a substituted or unsubstituted (optionally substituted) aromatic hydrocarbon group having from 6 to 25 carbon atoms. In this specification, the structural unit (A) represented by formula (1) is also referred to simply as "structural unit (A)" or "structural unit (A) according to the present invention." In addition, a silicon-containing arylamine polymer having the structural unit (A) represented by formula (1) is also referred to simply as "silicon-containing arylamine polymer" or "silicon-containing arylamine polymer according to the present invention."

[0018] In a second aspect, the present invention provides an electroluminescent device material comprising the silicon-containing arylamine polymer of the present invention.

[0019] In a third aspect, the present invention provides a composition for producing an electroluminescent device comprising two or more polymers, at least one of which is a silicon-containing arylamine polymer of the present invention.

[0020] In a fourth aspect, the present invention provides an electroluminescent device comprising a first electrode, a second electrode, and one or more organic films disposed between the first electrode and the second electrode, wherein at least one of the organic films comprises the silicon-containing arylamine polymer of the present invention. In this specification, the electroluminescent device is also referred to simply as "LED". The quantum dot electroluminescent device is also referred to simply as "QLED". The organic electroluminescent device is also referred to simply as "OLED".

[0021] Various low molecular weight materials and polymeric materials are used as materials for composing the light emitting layer and carrier transport layer of an electroluminescent element. Among these, low molecular weight materials are excellent in terms of efficiency and life of the element. However, when using low molecular weight materials, there is a problem that the manufacturing cost is high. On the other hand, as a polymeric material, TFB and the like are known as hole transport materials (for example, paragraph "0037" of Patent Document 1). However, it cannot be said that such polymeric materials have sufficient light emitting efficiency or sufficiently low driving voltage (see Comparative Example 1 below). For this reason, the development of a polymeric material capable of improving light emitting efficiency and reducing driving voltage was required. The present inventors have conducted extensive research into means for increasing the triplet energy level of a polymeric material (hence improving current efficiency and light emitting efficiency), which is a problem of the existing technology. As a result, it has been found that by applying a polymer having the structural unit (A) of the above formula (1) to an electroluminescent element, light emitting efficiency can be improved and a low driving voltage can be achieved compared to the case of using a known material. The mechanism by which the above-mentioned action and effect of the configuration of the present invention is exhibited is presumed to be as follows. In the structural unit (A) of the above formula (1), the silicon atom cuts the conjugation of the main chain. This increases the triplet energy level of the polymer compound, and high current efficiency can be achieved. Therefore, by using a polymer compound having the structural unit (A), an electroluminescence device that exhibits high luminous efficiency can be produced.

[0022] In addition, in the structural unit (A) of the above formula (1), the main chain is cut by a silicon atom. Therefore, even when the silicon-containing arylamine polymer of the present invention is polymerized, it exhibits properties similar to those of a low molecular weight compound whose energy level is close to that of a quantum dot. Therefore, by using the silicon-containing arylamine polymer of the present invention, it is possible to reduce the driving voltage.

[0023] Therefore, the silicon-containing arylamine polymer of the present invention has a high triplet energy level and can achieve high current efficiency. Therefore, an electroluminescence device prepared using the silicon-containing arylamine polymer of the present invention can exhibit high luminous efficiency. In addition, the silicon-containing arylamine polymer of the present invention can suppress an increase in driving voltage. Therefore, an electroluminescence device prepared using the silicon-containing arylamine polymer of the present invention can exhibit high luminous efficiency at a low driving voltage. In addition, since the silicon-containing arylamine polymer of the present invention has excellent film-forming properties and solvent solubility, it is possible to form a film by a wet (coating) method. Therefore, by using the silicon-containing arylamine polymer of the present invention, it is possible to increase the area of ​​the electroluminescence device and achieve high productivity. The above effect can be effectively exhibited when the silicon-containing arylamine polymer of the present invention is applied to an EL device, particularly a hole transport layer or hole injection layer of a QLED.

[0024] It should be noted that the above mechanism is merely speculation, and the present invention is not limited to the above mechanism.

[0025] Hereinafter, an embodiment of the present invention will be described. Note that the present invention is not limited to the following embodiment. In addition, the drawings are exaggerated for convenience of explanation, and the dimensional ratios of each component in each drawing may differ from the actual ratios. In addition, when the embodiment of the present invention is described with reference to the drawings, the same elements are given the same reference numerals in the description of the drawings, and duplicated explanations are omitted.

[0026] In this specification, unless otherwise specified, operations and measurements of physical properties are performed under conditions of room temperature (20° C. or higher and 25° C. or lower) and relative humidity of 40% RH or higher and 50% RH or lower.

[0027] [Silicon-containing arylamine polymer] The silicon-containing arylamine polymer of the present invention has a structural unit (A) represented by the following formula (1). A silicon-containing arylamine polymer having such a structural unit (A) has a high triplet energy level and can improve current efficiency. In addition, a low driving voltage can be achieved. The silicon-containing arylamine polymer of the present invention may contain one type of structural unit (A) or two or more types of structural units (A).

[0028] [ka]

[0029] In the above formula (1), Ar 1each independently represents a substituted or unsubstituted aromatic hydrocarbon group having 6 to 25 carbon atoms, or a substituted or unsubstituted heterocyclic aromatic group having 12 to 25 carbon atoms. Examples of the aromatic hydrocarbon group having 6 to 25 carbon atoms include, but are not limited to, monovalent groups derived from aromatic hydrocarbons such as benzene (phenyl group), pentalene, indene, naphthalene, anthracene, azulene, heptalene, acenaphthene, phenalene, fluorene, phenanthroline, biphenyl, terphenyl, quaterphenyl, quinquiphenyl, sexiphenyl, pyrene, 9,9-diphenylfluorene, 9,9'-spirobi[fluorene], and 9,9-dialkylfluorene. Examples of the heterocyclic aromatic group having 12 to 25 carbon atoms include, but are not limited to, monovalent groups derived from heterocyclic aromatic compounds such as acridine, phenazine, benzoquinoline, benzoisoquinoline, phenanthridine, phenanthroline, anthraquinone, fluorenone, dibenzofuran, dibenzothiophene, carbazole, imidazophenanthridine, benzimidazophenanthridine, azadibenzofuran, 9-phenylcarbazole, azacarbazole, azadibenzothiophene, diazadibenzofuran, diazacarbazole, diazadibenzothiophene, xanthone, thioxanthone, pyridine, quinoline, and anthraquinoline. 1 is preferably a monovalent radical derived from a compound selected from benzene, fluorene, biphenyl, p-terphenyl, 9,9-diphenylfluorene, 9,9'-spirobi[fluorene], dibenzofuran, dibenzothiophene and 9-phenylcarbazole. More preferably, both Ar 1 is preferably a monovalent radical derived from a compound selected from benzene, fluorene, biphenyl, p-terphenyl, 9,9-diphenylfluorene, 9,9'-spirobi[fluorene], dibenzofuran, dibenzothiophene and 9-phenylcarbazole. 1 is biphenyl. 1In the above preferred embodiment, a higher triplet energy level, a lower driving voltage, and a higher efficiency can be achieved. 1 may be unsubstituted or any hydrogen atom may be substituted with a substituent.

[0030] Here, Ar 1 The number of substituents introduced when any hydrogen atom of Ar is substituted is not particularly limited, but is preferably 1 or more and 3 or less, more preferably 1 or more and 2 or less, and particularly preferably 1. 1 When Ar has a substituent, the bonding position of the substituent is not particularly limited. 1 It is preferable that the substituent is located as far away as possible from the nitrogen atom in the main chain to which the substituent is linked. The presence of the substituent at such a position can achieve a higher triplet energy level, a lower driving voltage, and high efficiency.

[0031] Also, Ar 1 The substituent that may be present when any hydrogen atom of is substituted is not particularly limited, and examples thereof include alkyl groups, cycloalkyl groups, hydroxyalkyl groups, alkoxyalkyl groups, alkoxy groups, cycloalkoxy groups, alkenyl groups, alkynyl groups, amino groups, aryl groups, aryloxy groups, alkylthio groups, cycloalkylthio groups, arylthio groups, alkoxycarbonyl groups, aryloxycarbonyl groups, hydroxyl groups (-OH), carboxyl groups (-COOH), thiol groups (-SH), and cyano groups (-CN). In the above, they are not substituted with the same substituent. That is, the substituted alkyl groups are not substituted with alkyl groups.

[0032] Here, the alkyl group may be either linear or branched, and preferably includes linear or branched alkyl groups having from 1 to 18 carbon atoms. Specific examples include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, tert-pentyl, neopentyl, 1,2-dimethylpropyl, n-hexyl, isohexyl, 1,3-dimethylbutyl, 1-isopropylpropyl, 1,2-dimethylbutyl, n-heptyl, 1,4-dimethylpentyl, 3-ethylpentyl, 2-methyl-1-isopropylpropyl, Examples of such alkyl groups include 1-ethyl-3-methylbutyl group, n-octyl group, 2-ethylhexyl group, 3-methyl-1-isopropylbutyl group, 2-methyl-1-isopropyl group, 1-tert-butyl-2-methylpropyl group, n-nonyl group, 3,5,5-trimethylhexyl group, n-decyl group, isodecyl group, n-undecyl group, 1-methyldecyl group, n-dodecyl group, n-tridecyl group, n-tetradecyl group, n-pentadecyl group, n-hexadecyl group, n-heptadecyl group, and n-octadecyl group.

[0033] Examples of the cycloalkyl group include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, and a cyclohexyl group.

[0034] Examples of hydroxyalkyl groups include the above-mentioned alkyl groups substituted with 1 to 3 (preferably 1 to 2, particularly preferably 1) hydroxyl groups (eg, hydroxymethyl group, hydroxyethyl group).

[0035] Examples of the alkoxyalkyl group include the above-mentioned alkyl groups substituted with 1 to 3 (preferably 1 to 2, particularly preferably 1) of the above-mentioned alkoxy groups.

[0036] Examples of alkoxy groups include methoxy groups, ethoxy groups, propoxy groups, isopropoxy groups, butoxy groups, pentyloxy groups, hexyloxy groups, heptyloxy groups, octyloxy groups, nonyloxy groups, decyloxy groups, undecyloxy groups, dodecyloxy groups, tridecyloxy groups, tetradecyloxy groups, pentadecyloxy groups, hexadecyloxy groups, heptadecyloxy groups, octadecyloxy groups, 2-ethylhexyloxy groups, and 3-ethylpentyloxy groups.

[0037] Examples of the cycloalkoxy group include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, and a cyclohexyl group.

[0038] Examples of alkenyl groups include vinyl groups, allyl groups, 1-propenyl groups, isopropenyl groups, 1-butenyl groups, 2-butenyl groups, 3-butenyl groups, 1-pentenyl groups, 2-pentenyl groups, 3-pentenyl groups, 1-hexenyl groups, 2-hexenyl groups, 3-hexenyl groups, 1-heptenyl groups, 2-heptenyl groups, 5-heptenyl groups, 1-octenyl groups, 3-octenyl groups, and 5-octenyl groups.

[0039] Examples of the alkynyl group include an acetylenyl group, a 1-propynyl group, a 2-propynyl group, a 1-butynyl group, a 2-butynyl group, a 3-butynyl group, a 1-pentetyl group, a 2-pentetyl group, a 3-pentetyl group, a 1-hexynyl group, a 2-hexynyl group, a 3-hexynyl group, a 1-heptynyl group, a 2-heptynyl group, a 5-heptynyl group, a 1-octynyl group, a 3-octynyl group, and a 5-octynyl group.

[0040] Examples of the aryl group include a phenyl group, a naphthyl group, a biphenyl group, a fluorenyl group, anthryl group, a pyrenyl group, an azulenyl group, an acenaphthylenyl group, a terphenyl group, and a phenanthryl group.

[0041] Examples of the aryloxy group include a phenoxy group and a naphthyloxy group.

[0042] Examples of the alkylthio group include a methylthio group, an ethylthio group, a propylthio group, a pentylthio group, a hexylthio group, an octylthio group, and a dodecylthio group.

[0043] Examples of the cycloalkylthio group include a cyclopentylthio group and a cyclohexylthio group.

[0044] Examples of the arylthio group include a phenylthio group and a naphthylthio group.

[0045] Examples of the alkoxycarbonyl group include a methyloxycarbonyl group, an ethyloxycarbonyl group, a butyloxycarbonyl group, an octyloxycarbonyl group, and a dodecyloxycarbonyl group.

[0046] Examples of the aryloxycarbonyl group include a phenyloxycarbonyl group and a naphthyloxycarbonyl group.

[0047] That is, in a preferred embodiment of the present invention, Ar 1 are each independently a group selected from the following group. In the following structure, R 111 ~R 134each independently represents a hydrogen atom, a linear or branched alkyl group having from 1 to 12 carbon atoms, or a substituted or unsubstituted aromatic hydrocarbon group having from 6 to 25 carbon atoms. Examples of the linear or branched alkyl group having from 1 to 12 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a tert-pentyl group, a neopentyl group, a 1,2-dimethylpropyl group, an n-hexyl group, an isohexyl group, a 1,3-dimethylbutyl group, a 1-isopropylpropyl group, a 1,2-dimethylbutyl group, an n-heptyl group, Examples of the aromatic hydrocarbon group having 6 to 25 carbon atoms include, but are not limited to, the above-mentioned Ar. 1 From the viewpoint of achieving a higher triplet energy level and a lower driving voltage, R 111 ~R 134 is preferably a hydrogen atom or a linear or branched alkyl group having 2 to 10 carbon atoms. More preferably, R 111 ~R 134 is a hydrogen atom (unsubstituted) or a straight-chain alkyl group having 3 to 6 carbon atoms.

[0048] [ka]

[0049] In the above formula (1), Ar 2represents a substituted or unsubstituted divalent aromatic hydrocarbon group having 6 to 25 carbon atoms or a substituted or unsubstituted divalent heterocyclic aromatic group having 12 to 25 carbon atoms. Here, the divalent aromatic hydrocarbon group having 6 to 25 carbon atoms is not particularly limited, but may be any of the above-mentioned Ar 1 Similarly, the divalent heterocyclic aromatic group having 12 to 25 carbon atoms is not particularly limited, but may be any of the divalent groups defined in the above Ar 1 Examples of the divalent group include a heterocyclic aromatic compound having 12 to 25 carbon atoms as defined in the above. 2 is preferably a divalent radical derived from a compound selected from benzene, biphenyl, terphenyl, quaterphenyl, quinquiphenyl, sexiphenyl, fluorene, 9-phenylcarbazole, dibenzofuran, dibenzothiophene, 9,9-diphenylfluorene, and 9,9'-spirobi[fluorene]. More preferably, Ar 2 is preferably a divalent group derived from a compound selected from phenyl, biphenyl, terphenyl, quaterphenyl, quinquiphenyl, and fluorene. Particularly preferably, Ar 2 is preferably a divalent radical derived from a compound selected from biphenyl, p-terphenyl, p-quaterphenyl and p-quinquiphenyl. 2 is particularly preferably a divalent group derived from p-quinquiphenyl. 2 In the above preferred embodiment, a higher triplet energy level, a lower driving voltage, and a higher efficiency can be achieved. 2 may be unsubstituted or any hydrogen atom may be substituted with a substituent.

[0050] Here, Ar 2 The number of substituents introduced when any hydrogen atom of Ar is substituted is not particularly limited, but is preferably 1 or more and 3 or less, more preferably 1 or more and 2 or less, and particularly preferably 2. 2When has a substituent, the bonding position of the substituent is not particularly limited. For example, in the case of a plurality of substituents, the substituents are preferably present on the same aromatic ring or heterocycle, more preferably present on the same aromatic ring, and particularly preferably present on the same phenyl ring. Also, for example, when two substituents are present on a p-phenylene group, the two substituents may be present at any of the 2,3-position, 2,5-position, and 3,5-position, but are preferably present at the 2,5-position, 3,5-position, and particularly preferably present at the 2,5-position. Also, when a plurality of substituents are present on an aromatic ring or heterocycle to which a plurality of substituents are connected, the substituent is preferably present on an aromatic ring or heterocycle near the center. The presence of the substituent at such a position can achieve a higher triplet energy level, a lower driving voltage, and high efficiency.

[0051] Also, Ar 2 The substituent that may be present when any hydrogen atom of the above is substituted is not particularly limited, and may be any of the above-mentioned Ar 1 The same illustration can be applied.

[0052] That is, in a preferred embodiment of the present invention, Ar 2 is a divalent group selected from the following group. In the following structure, R 211 ~R 269 each independently represents a hydrogen atom, a linear or branched alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aromatic hydrocarbon group having 6 to 25 carbon atoms. Here, the linear or branched alkyl group having 1 to 12 carbon atoms, or the substituted or unsubstituted aromatic hydrocarbon group having 6 to 25 carbon atoms is not particularly limited, and can be any of the above R 111 ~R 134 From the viewpoint of achieving a higher triplet energy level and a lower driving voltage, R 211 ~R 269 is preferably a hydrogen atom or a linear or branched alkyl group having 2 to 10 carbon atoms. More preferably, R 211 ~R 269 is a hydrogen atom (unsubstituted) or a straight-chain alkyl group having 3 to 6 carbon atoms.

[0053] [ka]

[0054] In addition, in the above formula (1), R 1 each independently represents a hydrogen atom, a linear, branched or cyclic hydrocarbon group having 1 to 12 carbon atoms, or a substituted or unsubstituted aromatic hydrocarbon group having 6 to 25 carbon atoms. Here, the linear, branched or cyclic hydrocarbon group having 1 to 12 carbon atoms is not particularly limited, and examples thereof include linear or branched alkyl groups, alkenyl groups, alkynyl groups, and cycloalkyl groups. 1 When is an alkenyl or alkynyl group, R 1 The number of carbon atoms in R is 2 to 12. 1 When R is a cycloalkyl group, 1 The number of carbon atoms is 3 or more and 12 or less.

[0055] Examples of the alkyl group having 1 to 12 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a tert-pentyl group, a neopentyl group, a 1,2-dimethylpropyl group, an n-hexyl group, an isohexyl group, a 1,3-dimethylbutyl group, a 1-isopropylpropyl group, a 1,2-dimethylbutyl group, an n-heptyl group, a 1,4-dimethylbutyl group, a 1-isopropylpropyl group, a 1,2-dimethylbutyl group, an n-heptyl group, a 1,4-dimethylbutyl group, a 1-isopropylpropyl group, a 1,2-dimethylbutyl group, an n-hexyl group, an isohexyl group, a 1,3-dimethylbutyl group, a 1-isopropylpropyl group, a 1,2-dimethylbutyl group, an n-heptyl group, a 1,4-dimethylbutyl group, a 1-isopropyl ... Examples of such alkyl groups include ethylpentyl group, 3-ethylpentyl group, 2-methyl-1-isopropylpropyl group, 1-ethyl-3-methylbutyl group, n-octyl group, 2-ethylhexyl group, 3-methyl-1-isopropylbutyl group, 2-methyl-1-isopropyl group, 1-tert-butyl-2-methylpropyl group, n-nonyl group, 3,5,5-trimethylhexyl group, n-decyl group, isodecyl group, n-undecyl group, 1-methyldecyl group, and n-dodecyl group.

[0056] Examples of the alkenyl group having 2 to 12 carbon atoms include a vinyl group, an allyl group, a 1-propenyl group, a 2-butenyl group, a 1,3-butadienyl group, a 2-pentenyl group, and an isopropenyl group.

[0057] Examples of the alkynyl group having 2 to 12 carbon atoms include an ethynyl group and a propargyl group.

[0058] Examples of the cycloalkyl group having 3 to 12 carbon atoms include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, and a cyclohexyl group.

[0059] Of these, R 1 are each preferably independently a hydrogen atom or a linear or branched alkyl group having 1 to 12 carbon atoms. From the viewpoint of a higher triplet energy level and a lower driving voltage, R 1 is more preferably a hydrogen atom (unsubstituted) or a linear alkyl group having 3 to 6 carbon atoms.

[0060] The degree of polymerization of the structural unit (A) is not particularly limited, but is preferably an integer of 5 to 1,000. From the viewpoint of a higher triplet energy level and a lower driving voltage, the degree of polymerization of the structural unit (A) is more preferably 5 to 500, even more preferably 10 to 300, and particularly preferably 10 to 150.

[0061] In this embodiment, the structural unit (A) represented by formula (1) is preferably selected from the structural units represented by the following formulas (A-1) to (A-4) from the viewpoint of further improving the triplet energy level and hole transport ability and further reducing the driving voltage. Particularly preferably, the structural unit (A) represented by formula (1) is a structural unit represented by the following formula (A-1). In the following, "Alkyl" means "unsubstituted or substituted with an alkyl group". Preferably, "Alkyl" means unsubstituted (i.e., Alkyl = hydrogen atom) or substituted with a linear or branched alkyl group having 1 to 18 carbon atoms. More preferably, "Alkyl" means unsubstituted or substituted with a linear or branched alkyl group having 3 to 6 carbon atoms. In addition, "Alkyl" may be the same alkyl group or different alkyl groups.

[0062] [ka]

[0063] The composition of the structural unit (A) in the silicon-containing arylamine polymer of the present invention is not particularly limited. Considering the effect of further improving the hole transport ability of a layer (e.g., hole injection layer, hole transport layer) formed using the obtained silicon-containing arylamine polymer, the structural unit (A) is preferably 10 mol% or more and 100 mol% or less, more preferably 50 mol% or more and 100 mol% or less, particularly preferably 100 mol% with respect to all structural units constituting the silicon-containing arylamine polymer. That is, in a preferred embodiment of the present invention, the structural unit (A) is contained in a ratio of 10 mol% or more and 100 mol% or less with respect to all structural units. In a more preferred embodiment of the present invention, the structural unit (A) is contained in a ratio of 50 mol% or more and 100 mol% or less with respect to all structural units. In a particularly preferred embodiment of the present invention, the silicon-containing arylamine polymer is composed only of the structural unit (A) (i.e., the ratio of the structural unit (A) to all structural units=100 mol%). When the silicon-containing arylamine polymer contains two or more types of structural units (A), the content of the structural units (A) refers to the total amount of the structural units (A).

[0064] As described above, the silicon-containing arylamine polymer of the present invention may be composed of only the structural unit (A). Alternatively, the silicon-containing arylamine polymer of the present invention may further contain other structural units other than the structural unit (A). When other structural units are contained, the other structural units are not particularly limited as long as they do not inhibit the effects of the silicon-containing arylamine polymer (particularly high triplet energy level, low driving voltage). Specific examples include structural units selected from the following group. In the following, the structural units shown in the following group are also referred to as "structural unit (B)".

[0065] [ka]

[0066] The composition of the structural unit (B) in the silicon-containing arylamine polymer of this embodiment is not particularly limited. Considering the film-forming easiness and further improvement effect of the coating strength by the obtained polymer compound, the structural unit (B) is preferably 1 mol% or more and 10 mol% or less with respect to the total structural units constituting the silicon-containing arylamine polymer. Note that, when the silicon-containing arylamine polymer contains two or more kinds of structural units (B), the content of the structural unit (B) means the total amount of the structural units (B).

[0067] When the silicon-containing arylamine polymer is composed of two or more kinds of constitutional units, the structure of the silicon-containing arylamine polymer is not particularly limited. The silicon-containing arylamine polymer may be any of a random copolymer, an alternating copolymer, a periodic copolymer, and a block copolymer.

[0068] The weight average molecular weight (Mw) of the silicon-containing arylamine polymer is not particularly limited as long as the objective effect of the present invention can be obtained. The weight average molecular weight (Mw) is, for example, preferably 10,000 or more and 500,000 or less, more preferably 20,000 or more and 300,000 or less. With such a weight average molecular weight, it is possible to appropriately adjust the viscosity of the coating solution for forming a layer (e.g., hole injection layer, hole transport layer) using the silicon-containing arylamine polymer to form a layer with a uniform thickness.

[0069] In addition, the number average molecular weight (Mn) of the silicon-containing arylamine polymer is not particularly limited as long as the objective effect of the present invention can be obtained. The number average molecular weight (Mn) is, for example, preferably 10,000 to 500,000, more preferably 10,000 to 200,000. With such a number average molecular weight, it is possible to appropriately adjust the viscosity of the coating solution for forming a layer (e.g., hole injection layer, hole transport layer) using the silicon-containing arylamine polymer to form a layer with a uniform thickness. In addition, the polydispersity (weight average molecular weight / number average molecular weight) of the silicon-containing arylamine polymer of this embodiment is, for example, 1.2 to 4.0, preferably 1.5 to 3.5.

[0070] In this specification, the number average molecular weight (Mn) and weight average molecular weight (Mw) are not particularly limited, and can be measured by using a known method or by appropriately modifying a known method. In this specification, the number average molecular weight (Mn) and weight average molecular weight (Mw) are values ​​measured by the following method. The polydispersity (Mw / Mn) of a polymer is calculated by dividing the weight average molecular weight (Mw) by the number average molecular weight (Mn) measured by the following method.

[0071] (Measurement of number average molecular weight (Mn) and weight average molecular weight (Mw)) The number average molecular weight (Mn) and weight average molecular weight (Mw) of a polymeric material are measured by SEC (Size Exclusion Chromatography) using polystyrene as a standard substance under the following conditions.

[0072] (SEC measurement conditions) Analytical equipment (SEC): Shimadzu Corporation, Prominence Column: Polymer Laboratories, PLgel MIXED-B Column temperature: 40℃ Flow rate: 1.0mL / min Amount of sample solution injected: 20 μL (polymer concentration: approximately 0.05% by mass) Eluent: tetrahydrofuran (THF) Detector (UV-VIS detector): Shimadzu Corporation, SPD-10AV Standard sample: polystyrene.

[0073] The terminal of the main chain of the silicon-containing arylamine polymer of this embodiment is not particularly limited and is appropriately determined depending on the type of raw material used, but is usually a hydrogen atom.

[0074] The silicon-containing arylamine polymer of this embodiment can be synthesized by using a known organic synthesis method. A person skilled in the art can easily understand the specific synthesis method of the silicon-containing arylamine polymer of this embodiment by referring to the examples described below. Specifically, the silicon-containing arylamine polymer of this embodiment can be produced by a polymerization reaction using one or more monomers (1) represented by the following formula (1'), or by a copolymerization reaction using one or more monomers (1) represented by the following formula (1') and other monomers corresponding to the other structural units. The monomers used in the polymerization of the silicon-containing arylamine polymer can be synthesized by appropriately combining known synthesis reactions, and their structures are also confirmed by known methods (e.g., NMR, LC-MS, etc.).

[0075] [ka]

[0076] In the above formula (1'), Ar 1 and R 1 , R 2 is defined as in the above formula (1). 2’ and Ar 2” are bonded together to form Ar 2 Form X 1 and X 2 are each independently a halogen atom (a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, particularly a bromine atom) or a group having the following structure. In the following structure, R A ~R D are each independently an alkyl group having 1 to 3 carbon atoms. A ~R D is a methyl group.

[0077] [ka]

[0078] Alternatively, the silicon-containing arylamine polymer of this embodiment can be produced by a polymerization reaction using one or more monomers (1) represented by the following formula (1") and one or more monomers (2) represented by the following formula (2"), or by a copolymerization reaction using one or more monomers (1) represented by the following formula (1") and one or more monomers (2) represented by the following formula (2"), as well as other monomers corresponding to the other structural units described above.

[0079] [ka]

[0080] In the above formulas (1") and (2"), Ar 1 and R 1 , R 2 is defined as in the above formula (1). 2’ , Ar2” and Ar 2’” are bonded together to form Ar 2 Form X 1 and X 2 are each independently a halogen atom (a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, particularly a bromine atom) or a group having the following structure. In the following structure, R A ~R D are each independently an alkyl group having 1 to 3 carbon atoms. A ~R D is a methyl group. Note that X in the above formulas (1") and (2") 1 and X 2 may each be the same or different.

[0081] [ka]

[0082] The silicon-containing arylamine polymer of this embodiment has a structural unit (A). Therefore, it has a high triplet energy level and a low driving voltage. In addition, when the silicon-containing arylamine polymer of this embodiment is used as a hole injection material or a hole transport material (particularly a hole transport material), the current efficiency can be improved. Furthermore, when the silicon-containing arylamine polymer of this embodiment is used in an electroluminescence device, high charge mobility is achieved. Therefore, particularly when the silicon-containing arylamine polymer of this embodiment is used as a hole transport material, the deterioration effect on electrons can be reduced, and the device life (driving life) can be improved. Therefore, the electroluminescence device using the silicon-containing arylamine polymer of this embodiment has excellent luminous efficiency and durability. Furthermore, when the silicon-containing arylamine polymer of this embodiment has another structural unit having a crosslinkable group, the coating film stability can be improved. Therefore, the luminescence characteristics and stability can be improved when the electroluminescence device is formed in a laminated structure.

[0083] [Electroluminescence device materials] The silicon-containing arylamine polymer according to the present embodiment is preferably used as an electroluminescence device material. According to the silicon-containing arylamine polymer according to the present embodiment, an electroluminescence device material having a high triplet energy level (current efficiency) and a low driving voltage is provided. Also, according to the silicon-containing arylamine polymer according to the present embodiment, an electroluminescence device material having high charge mobility and excellent durability is provided. Furthermore, the main chain (the constituent unit of formula (1)) of the silicon-containing arylamine polymer has suitable flexibility. Therefore, the silicon-containing arylamine polymer according to the present embodiment exhibits high solubility in a solvent and high heat resistance. Therefore, it can be easily formed into a film (thin film) by a wet (coating) method. Therefore, in the second aspect, an electroluminescence device material containing the silicon-containing arylamine polymer of the present invention is provided. Or, the use of the silicon-containing arylamine polymer as an electroluminescence device material is provided.

[0084] In addition, the silicon-containing arylamine polymer of this embodiment has a HOMO level of more than 5.55 eV, particularly 5.57 eV or more. For this reason, the silicon-containing arylamine polymer of this embodiment can also be suitably used in quantum dot electroluminescence devices (particularly hole transport layers).

[0085] The electroluminescent device material according to this embodiment may further contain other polymers in addition to the silicon-containing arylamine polymer of the present invention. That is, in the third aspect, a composition for producing an electroluminescent device is provided, which comprises two or more polymers, at least one of which is the silicon-containing arylamine polymer of the present invention. Alternatively, use of a composition comprising two or more polymers including a silicon-containing arylamine polymer as an electroluminescent device material is provided. Hereinafter, the composition for producing an electroluminescent device according to the present invention is also referred to simply as "composition for LED" or "composition according to the present invention".

[0086] The object (or effect) of the present invention can also be achieved by the electroluminescence device material or composition according to this embodiment. The electroluminescence device material of this embodiment is an example of the electroluminescence device material according to the present invention. Similarly, the composition of this embodiment is an example of the composition according to the present invention.

[0087] Polymers other than the silicon-containing arylamine polymer of the present invention that can be used in the above third aspect are also referred to below simply as "other polymers".

[0088] In the third aspect, the structure of the other polymer is not particularly limited as long as it does not impair the effect of the present invention. Preferably, the other polymer has a constitutional unit represented by the following formula (A). By using a polymer (other polymer) having the above structure in combination with a silicon-containing arylamine polymer, the HOMO level and the LUMO level become closer to each other, and the charge injection barrier decreases (hence, the hole injection property is improved). Therefore, an electroluminescence device (particularly a QLED) using a combination of the silicon-containing arylamine polymer of the present invention and another polymer having a constitutional unit represented by the following formula (A) can improve its luminescence life. Note that the above mechanism is based on speculation, and its correctness does not affect the technical scope of the present invention.

[0089] That is, in a preferred embodiment of the present invention, at least one polymer has a constitutional unit represented by the following formula (A):

[0090] [ka]

[0091] wherein X is a group represented by the following formula (B), and Y is a substituted or unsubstituted divalent aromatic hydrocarbon group having 6 to 60 carbon atoms, or a substituted or unsubstituted divalent aromatic heterocyclic group having 3 to 60 ring atoms.

[0092] [ka]

[0093] However, Ar 100 is a substituted or unsubstituted trivalent aromatic hydrocarbon group having 6 to 60 carbon atoms, or a substituted or unsubstituted trivalent aromatic heterocyclic group having 3 to 60 ring atoms, Ar 200 and Ar 300 each independently represents a substituted or unsubstituted monovalent aromatic hydrocarbon group having from 6 to 60 carbon atoms, or a substituted or unsubstituted monovalent aromatic heterocyclic group having from 3 to 60 ring atoms, L 1 and L 2 each independently represents a single bond, a substituted or unsubstituted divalent aromatic hydrocarbon group having from 6 to 60 carbon atoms, or a substituted or unsubstituted divalent aromatic heterocyclic group having from 3 to 60 ring atoms, Z 1 ~Z 8 are each independently a nitrogen atom or -CH=, 5 ~Z 8 is -CH= and the hydrogen atom of said -CH= is -L 2 -N(Ar 200 )(Ar300 ), R 100 and R 200 each independently represents a substituted or unsubstituted alkyl group having from 1 to 20 carbon atoms, a substituted or unsubstituted alkoxy group having from 1 to 20 carbon atoms, a substituted or unsubstituted monovalent aromatic hydrocarbon group having from 6 to 60 carbon atoms, or a substituted or unsubstituted monovalent aromatic heterocyclic group having from 3 to 60 ring atoms, R 100 and R 200 may be bonded to each other to form a ring, a is an integer between 0 and 4, b is an integer between 0 and 3, If a is an integer between 1 and 4, Z 1 ~Z 4 is -CH= and the hydrogen atom of said -CH= is R 100 and when b is an integer between 1 and 3, Z 5 ~Z 8 is -CH= and the hydrogen atom of said -CH= is R 200 is replaced by.

[0094] Other polymers according to the above preferred embodiment will be described below. Note that the present invention is not limited to the following embodiment.

[0095] In this embodiment, the other polymer contains a segment of an alternating copolymer of the constitutional unit represented by the above formula (A). Here, the other polymer may contain one type of X as a constitutional unit, or may contain two or more types of X. Similarly, the other polymer may contain one type of Y as a constitutional unit, or may contain two or more types of Y.

[0096] In the above formula (A), X contains a nitrogen-containing aromatic heterocycle (e.g., a carbazole skeleton) substituted with an amino group. Therefore, when another polymer is used in combination with the silicon-containing arylamine polymer of the present invention in the hole transport layer of an electroluminescent device, the hole transport property can be further improved.

[0097] In addition, in another polymer according to this embodiment, X is an aromatic group (Ar 100 ), a nitrogen-containing aromatic heterocycle in the side chain and an amino group (N(Ar 200 )(Ar 300 For this reason, the other polymer according to the present embodiment has a deep HOMO level, and as a result, when used in a quantum dot light-emitting device, it can achieve higher luminous efficiency, lower driving voltage, and longer luminous lifetime.

[0098] In the above formula (B), Ar 100 is a substituted or unsubstituted trivalent aromatic hydrocarbon group having 6 to 60 carbon atoms, or a substituted or unsubstituted trivalent aromatic heterocyclic group having 3 to 60 ring atoms.

[0099] Here, the aromatic hydrocarbon group is a group derived from an aromatic hydrocarbon compound containing one or more aromatic hydrocarbon rings. Here, when the aromatic hydrocarbon group contains two or more aromatic hydrocarbon rings, the two or more aromatic hydrocarbon rings may be condensed with each other. In addition, the aromatic hydrocarbon group may be substituted with one or more substituents.

[0100] Examples of aromatic hydrocarbon compounds include, but are not limited to, benzene, pentalene, indene, naphthalene, anthracene, azulene, heptalene, acenaphthalene, phenalene, fluorene, anthraquinone, phenanthrene, biphenyl, triphenylene, pyrene, chrysene, picene, perylene, pentaphene, pentacene, tetraphene, hexaphene, hexacene, rubicene, trinaphthylene, heptaphene, and pyranthrene.

[0101] The aromatic heterocyclic group is a group derived from an aromatic heterocyclic compound containing one or more aromatic heterocycles having one or more heteroatoms (e.g., nitrogen atom (N), oxygen atom (O), phosphorus atom (P), sulfur atom (S)) and the remaining ring-forming atoms being carbon atoms (C). When the aromatic heterocyclic group contains two or more aromatic heterocycles, the two or more aromatic heterocycles may be condensed with each other. The aromatic heterocyclic group may be substituted with one or more substituents.

[0102] Examples of the aromatic heterocyclic compound include, but are not limited to, pyrazoline, imidazoline, oxazoline, thiazoline, triazoline, tetrazoline, oxadiazoline, pyridine, pyridazinine, pyrimidine, triazine, carbazoline, azacarbazoline, indoline, quinolinine, isoquinoline, benzimidazoline, imidazopyridine, imidazopyrimidine, furan, benzofuran, dibenzofuran, azadibenzofuran, thiophene, benzothiophene, dibenzothiophene, and azadibenzothiophene.

[0103] Ar 100 In the above formula, the trivalent aromatic hydrocarbon group may be a group in which any three hydrogen atoms have been removed from the hydrogen atoms of the aromatic hydrocarbon compound. In addition, the trivalent aromatic heterocyclic group may be a group in which any three hydrogen atoms have been removed from the hydrogen atoms of the aromatic heterocyclic compound.

[0104] Among these, Ar is used from the viewpoint of adjusting the HOMO level. 100 is preferably the group shown below.

[0105] [ka]

[0106] In the above structure, A is -O-, -S-, -Se-, -NR 1’ -(However, R 1’is a hydrogen atom, a deuterium atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted aryl group, or a substituted or unsubstituted heteroaryl group. 2’ R 3’ -(However, R 2’ and R 3’ are each independently a hydrogen atom, a deuterium atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted aryl group, or a substituted or unsubstituted heteroaryl group. ) and * is a bonding site.

[0107] When the trivalent aromatic hydrocarbon group or the trivalent aromatic heterocyclic group is substituted, the substituent is not particularly limited, and examples thereof include a halogen atom, an alkyl group, an alkoxy group, an aromatic hydrocarbon group, and an aromatic heterocyclic group, and two or more of these may be used in combination.

[0108] Here, examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.

[0109] Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a tert-pentyl group, a neopentyl group, a 1,2-dimethylpropyl group, an n-hexyl group, an isohexyl group, a 1,3-dimethylbutyl group, a 1-isopropylpropyl group, a 1,2-dimethylbutyl group, an n-heptyl group, a 1,4-dimethylpentyl group, a 3-ethylpentyl group, a 2-methyl-1-isopropylpropyl group, a 1-ethyl-3-methylbutyl group, an n-octyl group, Examples of such alkyl groups include 2-ethylhexyl, 3-methyl-1-isopropylbutyl, 2-methyl-1-isopropyl, 1-tert-butyl-2-methylpropyl, n-nonyl, 3,5,5-trimethylhexyl, n-decyl, isodecyl, n-undecyl, 1-methyldecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-pentadecyl, n-hexadecyl, n-heptadecyl, n-octadecyl, n-nonadecyl, n-eicosyl, n-heneicosyl, n-docosyl, n-tricosyl, and n-tetracosyl groups.

[0110] The alkyl group is preferably a linear or branched alkyl group having 1 to 24 carbon atoms, and more preferably a linear or branched alkyl group having 1 to 8 carbon atoms.

[0111] Examples of alkoxy groups include methoxy groups, ethoxy groups, propoxy groups, isopropoxy groups, butoxy groups, pentyloxy groups, hexyloxy groups, heptyloxy groups, octyloxy groups, nonyloxy groups, decyloxy groups, undecyloxy groups, dodecyloxy groups, tridecyloxy groups, tetradecyloxy groups, pentadecyloxy groups, hexadecyloxy groups, heptadecyloxy groups, octadecyloxy groups, 2-ethylhexyloxy groups, and 3-ethylpentyloxy groups.

[0112] The alkoxy group is preferably a linear or branched alkoxy group having 1 to 24 carbon atoms, and more preferably a linear or branched alkoxy group having 1 to 8 carbon atoms.

[0113] Examples of the aromatic heterocyclic group (or aromatic hydrocarbon group) that may be introduced into the trivalent aromatic hydrocarbon group (or trivalent aromatic heterocyclic group) include groups in which any one hydrogen atom has been removed from the above-mentioned aromatic heterocycles (or aromatic hydrocarbons).

[0114] In formula (B), Ar 200 and Ar 300 are each independently a substituted or unsubstituted monovalent aromatic hydrocarbon group having 6 to 60 carbon atoms, or a substituted or unsubstituted monovalent aromatic heterocyclic group having 3 to 60 ring atoms.

[0115] Here, the monovalent aromatic hydrocarbon group and the monovalent aromatic heterocyclic group are the same as Ar in formula (B), except that the trivalent aromatic hydrocarbon group and the trivalent aromatic heterocyclic group are monovalent. 100 In addition, when the monovalent aromatic hydrocarbon group or the monovalent aromatic heterocyclic group is substituted, the substituent is Ar 100 Since these are the same as the substituents in the above, the explanation will be omitted here.

[0116] From the viewpoint of increasing the HOMO level, hole transport property, and hole injection property of the other polymer according to this embodiment, the monovalent aromatic hydrocarbon group is preferably a phenyl group, a biphenyl group, a fluorenyl group, a naphthyl group, an anthryl group, a phenanthryl group, a naphthacenyl group, a pyrenyl group, a terphenyl group, a tolyl group, a t-butylphenyl group, or a (phenylpropyl)phenyl group, more preferably a phenyl group, a biphenyl group, a fluorenyl group, a naphthyl group, an anthryl group, a terphenyl group, or a tolyl group, and particularly preferably a biphenyl group or a fluorenyl group.

[0117] Furthermore, from the viewpoint of increasing the HOMO level, hole transport property, and hole injection property of the other polymer according to this embodiment, the monovalent aromatic heterocyclic group is preferably a pyridyl group, a bipyridyl group, a pyrrolyl group, a pyrazinyl group, a pyridinyl group, a pyrimidyl group, an indolyl group, a furyl group, a benzofuranyl group, a dibenzofuranyl group, a quinolyl group, a quinoxanyl group, a carbazolyl group, a phenanthridinyl group, an acridinyl group, a phenazinyl group, a phenothiazinyl group, a phenoxazinyl group, an oxazolyl group, an oxadiazolyl group, a furazanyl group, a thienyl group, a thiophenyl group, an isothiophenyl group, or a dibenzothiophenyl group, and more preferably a pyridyl group, a pyrrolyl group, a carbazolyl group, a dibenzofuranyl group, a dibenzothiophenyl group, or a bipyridyl group.

[0118] Furthermore, from the viewpoint of increasing the HOMO level, hole transport property, hole injection property, solubility, and coatability of the other polymer according to this embodiment, when the monovalent aromatic hydrocarbon group or the monovalent aromatic heterocyclic group is substituted, the substituent is preferably an alkyl group having 1 to 8 carbon atoms, an alkoxy group, an alkylthio group, an aryl group, an aryloxy group, an arylthio group, an arylalkyl group, an arylalkoxy group, an arylalkylthio group, an arylalkenyl group, an arylalkynyl group, an amino group, an amino group substituted with a substituent, a silyl group, a substituted silyl group, a halogen atom, an acyl group, an acyloxy group, an imine residue, an amide group, an acid imide group, a monovalent heterocyclic group, a carboxyl group, a carboxyl group substituted with a substituent, a cyano group, or a nitro group, and more preferably an alkyl group having 1 to 12 carbon atoms.

[0119] Ar 200 and Ar 300 Specific examples are shown below.

[0120] [ka]

[0121] [ka]

[0122] [ka]

[0123] In the above structure, R 3 are each independently a substituted or unsubstituted alkyl group having from 1 to 20 carbon atoms, a substituted or unsubstituted alkoxy group having from 1 to 20 carbon atoms, a substituted or unsubstituted monovalent aromatic hydrocarbon group having from 6 to 60 carbon atoms, or a substituted or unsubstituted monovalent aromatic heterocyclic group having from 3 to 60 ring atoms, * is a bonding site, and Alkyl means that it is substituted or unsubstituted with an alkyl group.

[0124] In the above formula (B), L 1 and L 2 are each independently a single bond, a substituted or unsubstituted divalent aromatic hydrocarbon group having from 6 to 60 carbon atoms, or a substituted or unsubstituted divalent aromatic heterocyclic group having from 3 to 60 ring atoms.

[0125] Here, the divalent aromatic hydrocarbon group and the divalent aromatic heterocyclic group are the same as Ar in formula (B), except that the trivalent aromatic hydrocarbon group and the trivalent aromatic heterocyclic group are divalent. 100 In addition, when the divalent aromatic hydrocarbon group or the divalent aromatic heterocyclic group is substituted, the substituent is Ar 100 Since these are the same as the substituents in the above, the explanation will be omitted here.

[0126] From the viewpoint of increasing the HOMO level, hole transport property, and hole injection property of the other polymer according to this embodiment, the divalent aromatic hydrocarbon group is preferably a phenylene group, a biphenylene group, a fluorenylene group, a naphthylene group, an anthrylene group, a phenanthrylene group, a naphthacenylene group, a pyrenylene group, a terphenylene group, a tolylene group, a t-butylphenylene group, or a (phenylpropyl)phenylene group, more preferably a phenylene group, a biphenylene group, a fluorenylene group, a naphthylene group, an anthrylene group, a terphenylene group, or a tolylene group, and particularly preferably a phenylene group.

[0127] In addition, from the viewpoint of increasing the HOMO level, hole transport property, and hole injection property of the other polymer according to this embodiment, the divalent aromatic heterocyclic group is preferably a pyridinediyl group, a bipyridinediyl group, a pyrrolinediyl group, a pyrazinediyl group, a pyridinyl group, a pyrimidinediyl group, an indolinediyl group, a furandiyl group, a benzofurandiyl group, a dibenzofurandiyl group, a quinolinediyl group, a quinoxalinediyl group, a carbazolediyl group, a phenanthridinediyl group, an acridinediyl group, or a cyclopentanediyl group.

[0043] Preferably, the aryl group is a phenazinediyl group, a phenothiazinediyl group, a phenoxazinediyl group, an oxazolediyl group, an oxadiazolediyl group, a furazandiyl group, a thiophenediyl group, a thiophenyl group, an isothiophenediyl group, or a dibenzothiophenediyl group, and more preferably a pyridinediyl group, a pyrrolinediyl group, a carbazolediyl group, a dibenzofurandiyl group, a dibenzothiophenediyl group, or a bipyridinediyl group.

[0128] Furthermore, from the viewpoint of increasing the HOMO level, hole transport property, hole injection property, solubility, and coatability of the other polymer according to this embodiment, when the divalent aromatic hydrocarbon group or the divalent aromatic heterocyclic group is substituted, the substituent is preferably an alkyl group having 1 to 50 carbon atoms, an alkoxy group, an alkylthio group, an aryl group, an aryloxy group, an arylthio group, an arylalkyl group, an arylalkoxy group, an arylalkylthio group, an arylalkenyl group, an arylalkynyl group, an amino group, an amino group substituted with a substituent, a silyl group, a substituted silyl group, a halogen atom, an acyl group, an acyloxy group, an imine residue, an amide group, an acid imide group, a monovalent heterocyclic group, a carboxyl group, a carboxyl group substituted with a substituent, a cyano group, or a nitro group, and more preferably an alkyl group having 1 to 50 carbon atoms.

[0129] Of these, L 1 and L 2 is preferably a single bond, a phenylene group, a biphenylene group, a fluorenylene group, a naphthylene group, an anthrylene group, a phenanthrylene group, a naphthacenylene group, a pyrenylene group, a terphenylene group, a tolylene group, a t-butylphenylene group, or a (phenylpropyl)phenylene group, more preferably a single bond, a phenylene group, a biphenylene group, a terphenylene group, or a fluorenylene group, and particularly preferably a single bond or a phenylene group.

[0130] In formula (B), Z constituting a nitrogen-containing aromatic heterocycle 1 ~Z 8 are each independently a nitrogen atom or -CH=. 5 ~Z 8 is -CH= and the hydrogen atom of said -CH= is -L 2 -N(Ar 200 )(Ar 300 ), i.e., Z 5 ~Z 8 Either -C[-L 2 -N(Ar 200 )(Ar 300 )]=.

[0131] In formula (B), R 100 and R 200 are each independently a substituted or unsubstituted alkyl group having from 1 to 20 carbon atoms, a substituted or unsubstituted alkoxy group having from 1 to 20 carbon atoms, a substituted or unsubstituted monovalent aromatic hydrocarbon group having from 6 to 60 carbon atoms, or a substituted or unsubstituted monovalent aromatic heterocyclic group having from 3 to 60 ring atoms. 100 and R 200 may be bonded to each other to form a ring. 100 and R 200 may be the same or different. In addition, when a is 2 or more and 4 or less, a plurality of R 100 may be the same or different. Similarly, when b is 2 or 3, multiple R 200 may be the same or different.

[0132] Here, the alkyl group having 1 to 20 carbon atoms is not particularly limited, but examples thereof include methyl group, ethyl group, n-propyl group, isopropyl group, n-butyl group, isobutyl group, sec-butyl group, tert-butyl group, n-pentyl group, isopentyl group, tert-pentyl group, neopentyl group, 1,2-dimethylpropyl group, n-hexyl group, isohexyl group, 1,3-dimethylbutyl group, 1-isopropylpropyl group, 1,2-dimethylbutyl group, n-heptyl group, 1,4-dimethylpentyl group, 3-ethylpentyl group, 2-methyl-1-isopropyl ... Examples of such alkyl groups include propylpropyl group, 1-ethyl-3-methylbutyl group, n-octyl group, 2-ethylhexyl group, 3-methyl-1-isopropylbutyl group, 2-methyl-1-isopropyl group, 1-tert-butyl-2-methylpropyl group, n-nonyl group, 3,5,5-trimethylhexyl group, n-decyl group, isodecyl group, n-undecyl group, 1-methyldecyl group, n-dodecyl group, n-tridecyl group, n-tetradecyl group, n-pentadecyl group, n-hexadecyl group, n-heptadecyl group, n-octadecyl group, and n-eicosyl group.

[0133] The alkyl group having 1 to 20 carbon atoms is preferably a linear or branched alkyl group having 1 to 20 carbon atoms, and more preferably a linear or branched alkyl group having 1 to 8 carbon atoms.

[0134] The alkoxy group having 1 to 20 carbon atoms is not particularly limited, but examples thereof include methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, sec-butoxy, tert-butoxy, n-pentoxy, isopentoxy, tert-pentoxy, neopentoxy, 1,2-dimethylpropoxy, n-hexyloxy, isohexyloxy, 1,3-dimethylbutoxy, 1-isopropylpropoxy, 1,2-dimethylbutoxy, n-heptyloxy, 1,4-dimethylpentyloxy, 3-ethylpentyloxy, 2-methyl-1-isopropylpropoxy, 1-methyl-2 ... Examples of such groups include an n-ethyl-3-methylbutoxy group, an n-octyloxy group, a 2-ethylhexyloxy group, a 3-methyl-1-isopropylbutoxy group, a 2-methyl-1-isopropoxy group, a 1-tert-butyl-2-methylpropoxy group, an n-nonyloxy group, a 3,5,5-trimethylhexyloxy group, an n-decyloxy group, an isodecyloxy group, an n-undecyloxy group, a 1-methyldecyloxy group, an n-dodecyloxy group, an n-tridecyloxy group, an n-tetradecyloxy group, an n-pentadecyloxy group, an n-hexadecyloxy group, an n-heptadecyloxy group, an n-octadecyloxy group, and an n-eicosyloxy group.

[0135] The alkoxy group having 1 to 20 carbon atoms is preferably a linear or branched alkoxy group having 1 to 20 carbon atoms, and more preferably a linear or branched alkoxy group having 1 to 8 carbon atoms.

[0136] Here, the monovalent aromatic hydrocarbon group having 6 to 60 carbon atoms and the monovalent aromatic heterocyclic group having 3 to 60 ring atoms are the same as Ar in formula (B), except that the trivalent aromatic hydrocarbon group and the trivalent aromatic heterocyclic group are monovalent. 100In addition, when an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a monovalent aromatic hydrocarbon group having 6 to 60 carbon atoms, or a monovalent aromatic heterocyclic group having 3 to 60 ring atoms is substituted, the substituent is Ar in formula (B). 100 Since these are the same as the substituents in the above, the explanation will be omitted here.

[0137] Of these, R 100 and R 200 is preferably a phenyl group or a fluorenyl group.

[0138] a is R in formula (B) 100 is the number of bonds to the nitrogen-containing aromatic heterocycle located in the side chain, and is an integer of 0 or more and 4 or less, preferably an integer of 0 or more and 2 or less, more preferably 0 or 1, and particularly preferably 0.

[0139] b is R in formula (B) 200 is the number of bonds to the nitrogen-containing aromatic heterocycle located in the side chain, and is an integer of 0 or more and 3 or less, preferably an integer of 0 or more and 2 or less, more preferably 0 or 1, and particularly preferably 0.

[0140] Here, if a is an integer between 1 and 4, Z 1 ~Z 4 is -CH= and the hydrogen atom of said -CH= is R 100 Therefore, R 100 Substituent (Z 1 ~Z 4 Similarly, when b is an integer between 1 and 3, Z 5 ~Z 8 is -CH= and the hydrogen atom of said -CH= is R 200 Therefore, R 200 Substituent (Z 5 ~Z 8 ) is -CH=.

[0141] The nitrogen-containing aromatic heterocycle preferably has the structure shown below: In the following structure, * indicates a binding site.

[0142] [ka]

[0143] In this embodiment, from the viewpoint of further improving the HOMO level and hole transport ability and further reducing the driving voltage, X is preferably selected from the structural units represented by the following formulas (2-1) to (2-6), and more preferably the following formula (2-1). Here, the multiple Xs contained in the segment of the alternating copolymer of the structural unit represented by the above formula (A) may be the same or different.

[0144] [ka]

[0145] In the above formulas (2-4) to (2-6), Ar 400 is a substituted or unsubstituted monovalent aromatic hydrocarbon group having 6 to 60 carbon atoms, or a substituted or unsubstituted monovalent aromatic heterocyclic group having 3 to 60 ring atoms.

[0146] Specific examples of X are shown below. In the following structures, * denotes a bonding site, and Alkyl means that the compound is unsubstituted or substituted with an alkyl group.

[0147] [ka]

[0148] [ka]

[0149] [ka]

[0150] [ka]

[0151] [ka]

[0152] [ka]

[0153] In this embodiment, the other polymer has a constitutional unit represented by -Y- in addition to the constitutional unit represented by the above formula (A). Here, the other polymer according to this embodiment may contain one type of Y or may contain two or more types of Y as a constitutional unit.

[0154] The other polymer according to this embodiment has excellent solubility because it contains Y as a structural unit. Therefore, when the other polymer according to this embodiment is used, a thin film can be easily formed by a coating method.

[0155] In formula (A), Y is a substituted or unsubstituted divalent aromatic hydrocarbon group having 6 to 60 carbon atoms, or a substituted or unsubstituted divalent aromatic heterocyclic group having 3 to 60 ring atoms.

[0156] Here, the divalent aromatic hydrocarbon group and the divalent aromatic heterocyclic group are the same as Ar in formula (B), except that the trivalent aromatic hydrocarbon group and the trivalent aromatic heterocyclic group are divalent. 100 Since it is similar to the above, the description will be omitted here.

[0157] Of these, from the viewpoint of improving the solubility of other polymers, Y is preferably a phenylene group, a fluorenediyl group, a biphenylene group, a fluorenylene group, a naphthylene group, an anthrylene group, a phenanthrylene group, a naphthacenylene group, a pyrenylene group, a terphenylene group, a tolylene group, a t-butylphenylene group, or a (phenylpropyl)phenylene group, more preferably a phenylene group or a fluorenediyl group, and particularly preferably a phenylene group.

[0158] In addition, when the divalent aromatic hydrocarbon group or the divalent aromatic heterocyclic group is substituted, the substituent is Ar 100 Since these are the same as the substituents in the above, the explanation will be omitted here.

[0159] Of these, from the viewpoint of improving the solubility of the other polymer according to this embodiment, the substituent is preferably a linear or branched alkyl group having from 1 to 20 carbon atoms, more preferably a linear or branched alkyl group having from 3 to 10 carbon atoms, and particularly preferably a linear alkyl group having from 6 to 8 carbon atoms.

[0160] From the viewpoint of adjusting the HOMO level, Y is preferably selected from the structural units represented by the following formulae (2-7) to (2-14). Of these, the other polymer preferably has a structural unit represented by the following formula (2-7). Here, the multiple Ys contained in the segment of the alternating copolymer of the structural unit represented by the above formula (A) may be the same or different.

[0161] [ka]

[0162] In the above formulas (2-7) to (2-14), Ar 51 ~Ar 55each independently represents a substituted or unsubstituted monovalent aromatic hydrocarbon group having from 6 to 60 carbon atoms, a substituted or unsubstituted monovalent aromatic heterocyclic group having from 3 to 60 ring atoms, an alkyl group having from 1 to 20 carbon atoms, or a hydrogen atom; A 11 ~A 13 are each independently -O-, -S-, -Se-, or -CR 3 R 4 -, -SiR 3 R 4 -(However, R 3 and R 4 are each independently a hydrogen atom, a deuterium atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted aryl group, or a substituted or unsubstituted heteroaryl group; A 21 ~A 28 are each independently -CR 5 =, -N=, -SiR 5 = (where R 5 is a hydrogen atom, a deuterium atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted aryl group, or a substituted or unsubstituted heteroaryl group.

[0163] Specific examples of Y are shown below. In the following structures, A is O, S, or Se, and when there are multiple Xs, the multiple Xs may be the same or different. * is a bonding site, and Alkyl means that it is substituted with an alkyl group.

[0164] [ka]

[0165] The other polymer according to this embodiment is preferably represented by the following formula (C), which extends the luminescence lifetime of the quantum dot light-emitting device.

[0166] [ka]

[0167] In the above formula (C), each E is independently a substituted or unsubstituted monovalent aromatic hydrocarbon group having 6 to 60 carbon atoms, or a substituted or unsubstituted monovalent aromatic heterocyclic group having 3 to 60 ring atoms, m is an integer of 2 or more, and a plurality of X's and Y's may each independently be the same or different.

[0168] Here, the monovalent aromatic hydrocarbon group and the monovalent aromatic heterocyclic group are the same as Ar in formula (B), except that the trivalent aromatic hydrocarbon group and the trivalent aromatic heterocyclic group are divalent. 100 In addition, when the monovalent aromatic hydrocarbon group or the monovalent aromatic heterocyclic group is substituted, the substituent is Ar 100 Since these are the same as the substituents in the above, the explanation will be omitted here.

[0169] Specific examples of E (terminal group) in the above formula (3) are shown below. In the following structures, * indicates a bonding site.

[0170] [ka]

[0171] Other polymers according to this embodiment can be used as materials for electroluminescent (EL) devices, but are particularly useful as hole transport materials for EL devices that include quantum dots.

[0172] The number average molecular weight (Mn) of the other polymer according to the present embodiment is preferably from 10,000 to 1,000,000, and more preferably from 30,000 to 500,000. This makes it possible to appropriately adjust the viscosity of a coating solution for forming a thin film containing the other polymer (e.g., a hole injection layer, a hole transport layer), and form a thin film of uniform thickness.

[0173] The weight average molecular weight (Mw) of the other polymer according to this embodiment is preferably 10,000 or more, and more preferably 50,000 or more and 500,000 or less, which makes it possible to appropriately adjust the viscosity of a coating solution for forming a thin film containing the other polymer (e.g., a hole injection layer, a hole transport layer) and form a thin film of uniform thickness.

[0174] The other polymer according to this embodiment can be synthesized by appropriately combining known organic synthesis reactions. A person skilled in the art can easily understand the specific synthesis method of the other polymer according to this embodiment by referring to the examples described below. Specifically, the other polymer according to this embodiment can be synthesized by copolymerizing one or more monomers (1) represented by the following formula (D) and one or more monomers (2) represented by the following formula (E) in a molar ratio of 1:1. The monomers (1) and (2) can be synthesized by appropriately combining known organic synthesis reactions. The monomers (1) and (2) can be identified using known analytical methods (e.g., NMR, LC-MS).

[0175] [ka]

[0176] In the above formulas (D) and (E), Ar 100 , Ar 200 , Ar 300 , L 1 , L 2 , R 100 , R 200 , a and b are the same as those in formula (B) above. 1 ~W 4 are each independently a halogen atom (a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, particularly a bromine atom) or a group having the following structure. In the following structure, R A ~R D are each independently an alkyl group having 1 to 3 carbon atoms. A ~R D is a methyl group.

[0177] [ka]

[0178] In the LED composition according to this embodiment, the mixing ratio of silicon-containing arylamine polymer and other polymer is not particularly limited as long as it does not impair the effect of the present invention. The mixing ratio of silicon-containing arylamine polymer and other polymer (silicon-containing arylamine polymer:other polymer (mass ratio)) is preferably more than 1:9 and less than 6:4, more preferably 2:8 or more and 4:6 or less. With such a mixing ratio, the charge mobility can be adjusted more easily, and the performance (e.g., luminous efficiency, luminous life) of LED element can be further improved.

[0179] [Electroluminescent element] As described above, the silicon-containing arylamine polymer or silicon-containing arylamine polymer and other polymers (compositions for LEDs) according to the present embodiment are suitably used in electroluminescence devices. That is, an electroluminescence device is provided that includes a pair of electrodes and one or more organic films disposed between the electrodes and containing the silicon-containing arylamine polymer or electroluminescence device material or composition for LEDs according to the present embodiment. Such an electroluminescence device can exhibit excellent luminous efficiency at a low driving voltage. Therefore, in a fourth aspect, the present invention provides an electroluminescence device that includes a first electrode, a second electrode, and one or more organic films disposed between the first electrode and the second electrode, wherein at least one layer of the organic film contains the silicon-containing arylamine polymer of the present invention or the composition for manufacturing an electroluminescence device of the present invention. The object (or effect) of the present invention can also be achieved by such an electroluminescence device according to the present embodiment. In a preferred embodiment of the above aspect, the electroluminescent element further includes a light-emitting layer disposed between the electrodes and containing a light-emitting material capable of emitting light from triplet excitons. The electroluminescent element of this embodiment is an example of the electroluminescent element according to the present invention.

[0180] Furthermore, the present embodiment provides a method for manufacturing an electroluminescence device comprising a pair of electrodes and one or more organic films disposed between the electrodes and containing the silicon-containing arylamine polymer of the present embodiment or the silicon-containing arylamine polymer and other polymers, wherein at least one of the organic films is formed by coating.Also, the present embodiment provides an electroluminescence device in which at least one of the organic films is formed by coating using this method.

[0181] The electroluminescence element material (EL element material) according to this embodiment has excellent solubility in organic solvents. Therefore, the EL element material according to this embodiment is particularly suitable for use in the manufacture of elements (particularly thin films) by a coating method (wet process). Therefore, this embodiment provides a liquid composition containing the silicon-containing arylamine polymer or the silicon-containing arylamine polymer according to this embodiment and other polymers, and a solvent or dispersion medium. Such a liquid composition is an example of the liquid composition according to the present invention.

[0182] In addition, the electroluminescent device material according to the embodiment as described above is preferably used for the manufacture of devices (particularly thin films) by coating method (wet process).From the above viewpoint, the present embodiment provides a thin film containing the silicon-containing arylamine polymer of the present embodiment or the silicon-containing arylamine polymer and other polymers.Such a thin film is an example of the thin film according to the present invention.

[0183] In addition, the EL element material or LED composition according to the present embodiment has excellent charge mobility. Therefore, it can be suitably used in the formation of any organic film such as a hole injection material, a hole transport material, or a light emitting material (host). Among these, it is suitably used as a hole injection material or a hole transport material from the viewpoint of hole transportability, and is particularly suitably used as a hole transport material.

[0184] That is, the present embodiment provides a composition comprising silicon-containing arylamine polymer or silicon-containing arylamine polymer and other polymer, and at least one material selected from the group consisting of hole transport material, electron transport material and luminescent material.Here, the luminescent material contained in the composition is not particularly limited, but can comprise organometallic complex (luminescent organometallic complex compound) or semiconductor nanoparticle (semiconductor inorganic nanoparticle).

[0185] [Electroluminescent element] The electroluminescent element according to the present embodiment will be described in detail below with reference to Fig. 1. Fig. 1 is a schematic diagram showing the electroluminescent element according to the present embodiment. In this specification, the "electroluminescent element" may be abbreviated to "EL element".

[0186] As shown in FIG. 1, the EL element 100 according to this embodiment includes a substrate 110, a first electrode 120 disposed on the substrate 110, a hole injection layer 130 disposed on the first electrode 120, a hole transport layer 140 disposed on the hole injection layer 130, an emitting layer 150 disposed on the hole transport layer 140, an electron transport layer 160 disposed on the emitting layer 150, an electron injection layer 170 disposed on the electron transport layer 160, and a second electrode 180 disposed on the electron injection layer 170.

[0187] Here, the silicon-containing arylamine polymer or silicon-containing arylamine polymer and other polymers of this embodiment are included in any organic film (organic layer) arranged between the first electrode 120 and the second electrode 180, for example. Specifically, the silicon-containing arylamine polymer or silicon-containing arylamine polymer and other polymers are preferably included in the hole injection layer 130 as a hole injection material, the hole transport layer 140 as a hole transport material, or the light-emitting layer 150 as a light-emitting material (host). It is more preferable that the silicon-containing arylamine polymer or silicon-containing arylamine polymer and other polymers are included in the hole injection layer 130 as a hole injection material or in the hole transport layer 140 as a hole transport material. It is particularly preferable that the silicon-containing arylamine polymer or silicon-containing arylamine polymer and other polymers are included in the hole transport layer 140 as a hole transport material. That is, in a preferred embodiment of the present invention, the organic film containing the silicon-containing arylamine polymer or silicon-containing arylamine polymer and other polymers is a hole transport layer, a hole injection layer, or a light-emitting layer. In a more preferred embodiment of the present invention, the organic film containing the silicon-containing arylamine polymer or the silicon-containing arylamine polymer and other polymers is a hole transport layer or a hole injection layer.In a particularly preferred embodiment of the present invention, the organic film containing the silicon-containing arylamine polymer or the silicon-containing arylamine polymer and other polymers is a hole transport layer.

[0188] In addition, the organic film containing the silicon-containing arylamine polymer / EL device material / LED composition (combination of silicon-containing arylamine polymer and other polymer) of this embodiment is formed by coating method (solution coating method).Specifically, the organic film is formed by using solution coating method such as spin coat method, casting method, micro gravure coat method, gravure coat method, bar coat method, roll coat method, wire bar coat method, dip coat method, spray coat method, screen printing method, flexographic printing method, offset printing method, ink jet printing method, etc.

[0189] In addition, the solvent used in the solution coating method can be any solvent that can dissolve the silicon-containing arylamine polymer / EL device material / LED composition (combination of silicon-containing arylamine polymer and other polymer), and can be appropriately selected depending on the type of silicon-containing arylamine polymer and other polymers used. For example, toluene, xylene, ethylbenzene, diethylbenzene, methylene, propylbenzene, cyclohexylbenzene, dimethoxybenzene, anisole, ethoxytoluene, phenoxytoluene, isopropylbiphenyl, dimethylanisole, phenyl acetate, phenyl propionate, methyl benzoate, ethyl benzoate, cyclohexane, etc. can be exemplified. In addition, the amount of the solvent used is not particularly limited, but considering the ease of coating, etc., the concentration of the silicon-containing arylamine polymer or the silicon-containing arylamine polymer and other polymers is preferably 0.1 mass% or more and 10 mass% or less, more preferably 0.5 mass% or more and 5 mass% or less. In the latter case, the concentration means the total concentration of the silicon-containing arylamine polymer and other polymers.

[0190] In addition, the method of forming the layer other than the organic film containing silicon-containing arylamine polymer / EL device material / composition for LED (combination of silicon-containing arylamine polymer and other polymer) is not particularly limited.The layer other than the organic film containing silicon-containing arylamine polymer / EL device material / composition for LED (combination of silicon-containing arylamine polymer and other polymer) of this embodiment may be formed by vacuum deposition method or solution coating method.

[0191] A substrate used in a general EL device can be used as the substrate 110. For example, the substrate 110 may be a glass substrate, a semiconductor substrate such as a silicon substrate, or a transparent plastic substrate.

[0192] A first electrode 120 is formed on the substrate 110. Specifically, the first electrode 120 is an anode, and is made of a metal, an alloy, a conductive compound, or the like that has a large work function. For example, the first electrode 120 is made of indium tin oxide (InO 2 ), which has excellent transparency and conductivity. 2 O 3 -SnO 2 :ITO), indium zinc oxide (In 2 O 3 The first electrode 120 may be formed as a transmissive electrode using tin oxide (ZnO), tin oxide (SnO2), zinc oxide (ZnO), or the like. The first electrode 120 may be formed as a reflective electrode by laminating magnesium (Mg), aluminum (Al), or the like on the transparent conductive film. After the first electrode 120 is formed on the substrate 110, cleaning and UV-ozone treatment may be performed, if necessary.

[0193] A hole injection layer 130 is formed on the first electrode 120. The hole injection layer 130 is a layer that facilitates the injection of holes from the first electrode 120, and may be formed to a thickness of about 10 nm to about 1000 nm, more specifically, about 20 nm to about 50 nm (dry film thickness; the same applies below).

[0194] The hole injection layer 130 can be formed of a known hole injection material. Examples of known hole injection materials for forming the hole injection layer 130 include poly(ether ketone)-containg triphenylamine (TPAPEK), 4-isopropyl-4'-methyldiphenyliodonium tetrakis(pentafluorophenyl)borate (PPBI), N,N'-diphenyl-N,N'-bis-[4-(phenyl-m-tolyl-amino)-phenyl]-biphenyl-4,4'-diamine (DNTPD), copper phthalocyanine (CuPc), and the like. phthalocyanine), 4,4',4”-tris(3-methylphenylphenylamino)triphenylamine (m-MTDATA), N,N'-di(1-naphthyl)-N,N'-diphenylbenzidine (NPB), 4,4',4”-tris(diphenylamino)triphenylamine (TDATA), 4,4',4”-tris(N,N-2-naphthylphenylamino)triphenylamine (2-TNATA), polyaniline / dodecylbenzenesulphonic acid acid), poly(3,4-ethylenedioxythiophene) / poly(4-styrenesulfonate) (poly(3,Examples of such a polymer include 4-ethylenedioxythiophene / poly(4-styrenesulfonate):PEDOT / PSS, and polyaniline / 10-camphorsulfonic acid.

[0195] On the hole injection layer 130, a hole transport layer 140 is formed. The hole transport layer 140 is a layer having a function of transporting holes, and may be formed, for example, with a thickness of about 10 nm to about 150 nm, more specifically, about 20 nm to about 50 nm. The hole transport layer 140 is preferably formed by a solution coating method using the silicon-containing arylamine polymer of this embodiment or the silicon-containing arylamine polymer and other polymers. This method can improve the current efficiency of the EL device 100 and reduce the driving voltage. In addition, since the hole transport layer can be formed by a solution coating method, it can be efficiently formed over a large area.

[0196] However, when any other organic film of the EL element 100 contains the silicon-containing arylamine polymer of this embodiment or the silicon-containing arylamine polymer and other polymers, the hole transport layer 140 may be formed of a known hole transport material. Examples of known hole transport materials include carbazole derivatives such as 1,1-bis[(di-4-tolylamino)phenyl]cyclohexane (TAPC), N-phenylcarbazole, and polyvinylcarbazole, and N,N'-bis(3-methylphenyl)-N,N'-diphenyl-[1,1-biphenyl]-4,4'-diamine (N ,N'-bis(3-methylphenyl)-N,N'-diphenyl-[1,1-biphenyl]-4,4'-diamine (TPD), 4,4',4"-tris(N-carbazolyl)triphenylamine (TCTA), and N,N'-di(1-naphthyl)-N,N'-diphenylbenzidine (NPB).

[0197] The light-emitting layer 150 is formed on the hole transport layer 140. The light-emitting layer 150 is a layer that emits light by fluorescence, phosphorescence, or the like, and is formed by using a vacuum deposition method, a spin coating method, an inkjet printing method, or the like. The light-emitting layer 150 may be formed to a thickness of, for example, about 10 nm or more and about 60 nm or less, more specifically, about 20 nm or more and about 50 nm or less. As the light-emitting material of the light-emitting layer 150, a known light-emitting material can be used. However, the light-emitting material contained in the light-emitting layer 150 is preferably a light-emitting material that can emit light from triplet excitons (i.e., phosphorescence emission). In such a case, the driving life of the EL element 100 can be further improved.

[0198] The light-emitting layer 150 is not particularly limited and may have a known configuration. Preferably, the light-emitting layer contains semiconductor nanoparticles or an organometallic complex. That is, in a preferred embodiment of the present invention, the organic film has a light-emitting layer containing semiconductor nanoparticles or an organometallic complex. When the light-emitting layer contains semiconductor nanoparticles, the EL element is a quantum dot electroluminescent element (QLED), a quantum dot light-emitting element, or a quantum dot light-emitting element. When the light-emitting layer contains an organometallic complex, the EL element is an organic electroluminescent element (OLED).

[0199] In the case of a configuration (QLED) in which the light-emitting layer contains semiconductor nanoparticles, the light-emitting layer is a single layer or multiple layers of a large number of semiconductor nanoparticles (quantum dots). Here, the semiconductor nanoparticles (quantum dots) are particles of a certain size that have a quantum confinement effect. The diameter of the semiconductor nanoparticles (quantum dots) is not particularly limited, but is about 1 nm or more and 10 nm or less.

[0200] The semiconductor nanoparticles (quantum dots) arranged in the light-emitting layer can be synthesized by a wet chemical process, a metalorganic chemical vapor deposition process, a molecular beam epitaxy process, or other similar processes, etc. Among them, the wet chemical process is a method in which a precursor material is put into an organic solvent to grow particles.

[0201] In the wet chemical process, the organic solvent naturally coordinates with the surface of the quantum dot crystals as the crystals grow, and acts as a dispersant to regulate the growth of the crystals. Therefore, the wet chemical process can control the growth of semiconductor nanoparticles more easily and at lower cost than gas phase deposition methods such as Metal Organic Chemical Vapor Deposition (MOCVD) and Molecular Beam Epitaxy (MBE).

[0202] By adjusting the size of semiconductor nanoparticles (quantum dots), the energy band gap can be adjusted, and light of various wavelengths can be obtained in the light-emitting layer (quantum dot light-emitting layer). Therefore, by using multiple quantum dots of different sizes, it is possible to realize a display that emits (or emits) light of multiple wavelengths. The size of the quantum dots can be selected to emit red, green, and blue light so that a color display can be constructed. The sizes of the quantum dots can also be combined to emit various color lights to emit white light.

[0203] As the semiconductor nanoparticles (quantum dots), a semiconductor material selected from the group consisting of II-VI group semiconductor compounds; III-V group semiconductor compounds; IV-VI group semiconductor compounds; IV group elements or compounds; and combinations thereof can be used.

[0204] The II-VI semiconductor compound is not particularly limited, but may be selected from the group consisting of two-element compounds selected from the group consisting of CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, and mixtures thereof; three-element compounds selected from the group consisting of CdSeS, CdSeTe, CdSTe, ZnSeS, ZnTeSe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, and mixtures thereof; and four-element compounds selected from the group consisting of CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe, and mixtures thereof.

[0205] The III-V semiconductor compound is not particularly limited, but may be selected from the group consisting of two-element compounds selected from the group consisting of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, and mixtures thereof; three-element compounds selected from the group consisting of GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, and mixtures thereof; and four-element compounds selected from the group consisting of GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb, and mixtures thereof.

[0206] The IV-VI semiconductor compound is not particularly limited, and may be selected from the group consisting of binary compounds selected from the group consisting of SnS, SnSe, SnTe, PbS, PbSe, PbTe, and mixtures thereof; ternary compounds selected from the group consisting of SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, and mixtures thereof; and quaternary compounds selected from the group consisting of SnPbSSe, SnPbSeTe, SnPbSTe, and mixtures thereof.

[0207] The Group IV element or compound is not particularly limited, but may be selected from the group consisting of mono-element compounds selected from the group consisting of Si, Ge, and mixtures thereof; and bi-element compounds selected from the group consisting of SiC, SiGe, and mixtures thereof.

[0208] Semiconductor nanoparticles (quantum dots) can have a homogeneous single structure or a core-shell double structure. The core and shell can contain different materials. The materials constituting each core and shell can be made of different semiconductor compounds. However, the energy band gap of the shell material is larger than that of the core material. Specifically, structures such as ZnTeSe / ZnSe / ZnS, InP / ZnSe / ZnS, CdSe / ZnS, and InP / ZnS are preferred.

[0209] For example, we will explain how to fabricate quantum dots with a core (CdSe)-shell (ZnS) structure. First, we add (CH 3 ) 2 Precursors for the core (CdSe), such as Cd(dimethylcadmium) and TOPSe(trioctylphosphine selenide), are injected to generate crystals. At this time, the crystals are maintained at high temperature for a certain time so that they grow to a certain size, and then the precursor for the shell (ZnS) is injected to form a shell on the surface of the already generated core. This allows the creation of CdSe / ZnS quantum dots capped with TOPO.

[0210] In the case of an OLED in which the light-emitting layer includes an organic metal complex, the light-emitting layer 150 may include, as a host material, for example, 6,9-diphenyl-9'-(5'-phenyl-[1,1':3',1"-terphenyl]-3-yl)3,3'-bi[9H-carbazole], 3,9-diphenyl-5-(3-(4-phenyl-6-(5'-phenyl-[1,1':3',1"-terphenyl]-3-yl)-1,3,5,-triazine-2-yl )phenyl)-9H-carbazole, 9,9'-diphenyl-3,3'-bi[9H-carbazole], tris(8-quinolinato)aluminium (Alq3), 4,4'-bis(carbazol-9-yl)biphenyl (CBP), poly(n-vinyl carbazole) carbazole (PVK), 9,10-di(naphthalene)anthracene (ADN), 4,4',4”-tris(N-carbazolyl)triphenylamine (TCTA), 1,3,5-tris(N-phenyl-benzimidazol-2-yl)benzene (1,3,5-tris(N-phenyl-benzimidazol-2-yl)benzene (1,3,5-tris(N-phenyl-benzimidazol-2-yl)benzene) 3-tert-butyl-9,10-di(naphth-2-yl)anthracene (TPBI), 3-tert-butyl-9,10-di(naphth-2-yl)anthracene (TBADN), distyrylarylene (DSA), 4,4'-bis(9-carbazole)2,2'-dimethyl-biphenyl (dmCBP), and the like.

[0211] The light-emitting layer 150 may contain, as a dopant material, for example, perylene and its derivatives, rubrene and its derivatives, coumarin and its derivatives, 4-dicyanomethylene-2-(pdimethylaminostyryl)-6-methyl-4H-pyran (DCM) and its derivatives, bis[2-(4,6-difluorophenyl)pyridinate]picolinate iridium(III):FIrpic, bis(1-phenylisoquinoline)(acetylacetonate)iridium(III):Ir(piq), 2 (acac)), tris(2-phenylpyridine)iridium(III):Ir(ppy) 3 ), iridium (Ir) complexes such as tris(2-(3-p-oxyyl)phenyl)pyridineiridium(III), osmium (Os) complexes, platinum complexes, etc. Of these, it is preferable that the light-emitting material is a light-emitting organometallic complex compound.

[0212] The method for forming the light-emitting layer is not particularly limited. It can be formed by applying a coating solution containing semiconductor nanoparticles or an organometallic complex (solution coating method). In this case, it is preferable to select a solvent that does not dissolve the material in the hole transport layer (hole transport material, particularly silicon-containing arylamine polymer or silicon-containing arylamine polymer and other polymer) as the solvent constituting the coating solution.

[0213] An electron transport layer 160 is formed on the light emitting layer 150. The electron transport layer 160 is a layer having a function of transporting electrons, and is formed by using a vacuum deposition method, a spin coating method, an ink jet method, or the like. The electron transport layer 160 may be formed to a thickness of, for example, about 15 nm or more and about 50 nm or less.

[0214] The electron transport layer 160 may be formed of a known electron transport material. Examples of known electron transport materials include (8-quinolinolato) lithium (lithium quinolate) (Liq), tris(8-quinolinolato)aluminum (Alq), and the like. 3 ), and compounds having a nitrogen-containing aromatic ring. Specific examples of the compound having a nitrogen-containing aromatic ring include a compound having a pyridine ring such as 1,3,5-tri[(3-pyridyl)-phen-3-yl]benzene, a compound having a triazine ring such as 2,4,6-tris(3'-(pyridin-3-yl)biphenyl-3-yl)-1,3,5-triazine, and a compound having a 2-(4-(N-phenylbenzoyl)phenyl)-1,3,5-triazine. Examples of the electron transport material include compounds containing an imidazole ring such as 2-(4-(N-phenylbenzoimidazolyl-1-yl-phenyl)-9,10-dinaphthylanthracene and 1,3,5-tris(N-phenyl-benzimidazol-2-yl)benzene (TPBI). The above electron transport materials may be used alone or as a mixture of two or more kinds.

[0215] An electron injection layer 170 is formed on the electron transport layer 160. The electron injection layer 170 is a layer having a function of facilitating the injection of electrons from the second electrode 180. The electron injection layer 170 is formed by using a vacuum deposition method or the like. The electron injection layer 170 may be formed to a thickness of about 0.1 nm to about 5 nm, more specifically, about 0.3 nm to about 2 nm. Any known material can be used to form the electron injection layer 170. For example, the electron injection layer 170 can be formed using a lithium compound such as (8-quinolinato)lithium (Liq) and lithium fluoride (LiF), sodium chloride (NaCl), cesium fluoride (CsF), lithium oxide (Li 2 O), barium oxide (BaO), or the like.

[0216] The second electrode 180 is formed on the electron injection layer 170. The second electrode 180 is formed by using a vacuum deposition method or the like. The second electrode 180 is specifically a cathode, and is formed of a metal, an alloy, a conductive compound, or the like that has a small work function. For example, the second electrode 180 may be formed as a reflective electrode using a metal such as lithium (Li), magnesium (Mg), aluminum (Al), or calcium (Ca), or an alloy such as aluminum-lithium (Al-Li), magnesium-indium (Mg-In), or magnesium-silver (Mg-Ag). The second electrode 180 may be formed to a thickness of about 10 nm to about 200 nm, more specifically, about 50 nm to about 150 nm. Alternatively, the second electrode 180 may be formed of a thin film of 20 nm or less of the above metal materials, indium tin oxide (In 2 O 3 -SnO 2 ) and indium zinc oxide (In 2 O 3 Alternatively, the transparent electrode may be formed of a transparent conductive film such as ZnO.

[0217] The EL element 100 according to this embodiment has been described above as an example of the electroluminescence element according to the present invention. The organic EL element 100 according to this embodiment can further improve the luminous efficiency (current efficiency) and reduce the driving voltage by providing an organic film (particularly a hole transport layer or a hole injection layer) containing a silicon-containing arylamine polymer or a silicon-containing arylamine polymer and another polymer. In particular, in the latter case, the luminous efficiency can be maintained for a long period of time (the luminous life can be improved).

[0218] The laminated structure of the EL element 100 according to the present embodiment is not limited to the above example. The EL element 100 according to the present embodiment may be formed with other known laminated structures. For example, the EL element 100 may omit one or more layers among the hole injection layer 130, the hole transport layer 140, the electron transport layer 160, and the electron injection layer 170, or may additionally include other layers. Each layer of the EL element 100 may be formed as a single layer or as a multiple layer structure.

[0219] For example, the EL device 100 may further include a hole blocking layer between the hole transport layer 140 and the light emitting layer 150 in order to prevent excitons or holes from diffusing into the electron transport layer 160. The hole blocking layer may be formed of, for example, an oxadiazole derivative, a triazole derivative, or a phenanthroline derivative.

[0220] Furthermore, the silicon-containing arylamine polymer or silicon-containing arylamine polymer and other polymers according to this embodiment can be applied to electroluminescence devices other than the above-mentioned QLED or OLED.The other electroluminescence devices that can be applied to the silicon-containing arylamine polymer or silicon-containing arylamine polymer and other polymers according to this embodiment are not particularly limited, and can include, for example, organic-inorganic perovskite light-emitting devices. EXAMPLES

[0221] The effects of the present invention will be described using the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples. In the following examples, unless otherwise specified, the operations were performed at room temperature (25°C). Furthermore, unless otherwise specified, "%" and "parts" mean "% by mass" and "parts by mass", respectively.

[0222] Synthesis Example 1 (Synthesis of Compound A-1 and Compound A-2) Compound A-1 and Compound A-2 were synthesized according to the following reactions.

[0223] [ka]

[0224] Into a four-neck flask purged with argon, bis(4-bromophenyl)diphenylsilane (10.5 g), 4'-propyl-[1,1'-biphenyl]-4-amine (10.5 g), tris(dibenzylideneacetone)dipalladium (Pd 2 (dba) 3 ) (0.371 g), 1,1'-bis(diphenylphosphino)ferrocene (DPPF) (0.448 g), sodium tert-butoxide (t-BuONa) (5.83 g), and toluene (200 mL) were added and heated at 95°C for 2 hours. The mixture was allowed to cool to room temperature (25°C; the same applies below), and insoluble matter was filtered off using Celite (registered trademark, the same applies below). The solvent was removed from the filtrate under reduced pressure, and the mixture was purified by column chromatography to obtain compound A-1 (11.5 g).

[0225] In a four-neck flask purged with argon, compound A-1 (10.0 g), 4-bromo-4'-iodo-1,1'-biphenyl (14.2 g), tris(dibenzylideneacetone)dipalladium (Pd 2 (dba) 3) (0.606 g), 1,1'-bis(diphenylphosphino)ferrocene (DPPF) (1.47 g), sodium tert-butoxide (t-BuONa) (5.09 g), and xylene (200 mL) were added and heated at 120°C for 2 hours. The mixture was allowed to cool to room temperature, and insoluble matter was filtered off using Celite. The solvent was removed from the filtrate under reduced pressure, and the mixture was purified by column chromatography to obtain compound A-2 (9.50 g).

[0226] Synthesis Example 2 (Synthesis of Compound B-1) Compound B-1 was synthesized according to the following reaction.

[0227] [ka]

[0228] Into a four-neck flask purged with argon, add N,N'-((diphenylsilanediyl)bis(4,1-phenylene )) (Bis(4'-propyl[1,1'-biphenyl]-4-amine )) (10.0 g), 4-bromo-1-iodobenzene (11.2 g), tris(dibenzylideneacetone)dipalladium (Pd 2 (dba) 3 ) (0.606 g), 1,1'-bis(diphenylphosphino)ferrocene (DPPF) (1.47 g), sodium tert-butoxide (t-BuONa) (5.09 g), and xylene (130 mL) were added and heated at 120°C for 2 hours. The mixture was allowed to cool to room temperature, and insoluble matter was filtered off using Celite. The solvent was removed from the filtrate under reduced pressure, and the mixture was purified by column chromatography to obtain compound B-1 (8.60 g).

[0229] Synthesis Example 3 (Synthesis of compound C-1) Compound C-1 was synthesized according to the following reaction.

[0230] [ka]

[0231] Into a four-neck flask purged with argon, bis(4-bromophenyl)diphenylsilane (10.5 g), 4'-hexyl-[1,1'-biphenyl]-4-amine (12.6 g), tris(dibenzylideneacetone)dipalladium (Pd 2 (dba) 3 ) (0.371 g), 1,1'-bis(diphenylphosphino)ferrocene (DPPF) (0.448 g), sodium tert-butoxide (t-BuONa) (5.83 g), and toluene (200 mL) were added and heated at 95°C for 2 hours. The mixture was allowed to cool to room temperature, and the insoluble matter was filtered off using Celite. The solvent was removed from the filtrate under reduced pressure, and the mixture was purified by column chromatography to obtain N,N'-((diphenylsilanediyl)bis(4,1-phenylene))(bis(4'-hexyl[1,1'-biphenyl]-4-amine)) (12.5 g).

[0232] Into a four-neck flask purged with argon, add N,N'-((diphenylsilanediyl)bis(4,1-phenylene )) (Bis(4'-hexyl[1,1'-biphenyl]-4-amine )) (10.0 g), 4-bromo-1-iodobenzene (14.2 g), tris(dibenzylideneacetone)dipalladium (Pd 2 (dba) 3 ) (0.606 g), 1,1'-bis(diphenylphosphino)ferrocene (DPPF) (1.47 g), sodium tert-butoxide (t-BuONa) (5.09 g), and xylene (200 mL) were added and heated at 120°C for 2 hours. The mixture was allowed to cool to room temperature, and insoluble matter was filtered off using Celite. The solvent was removed from the filtrate under reduced pressure, and the mixture was purified by column chromatography to obtain compound C-1 (10.80 g).

[0233] Synthesis Example 4 (Synthesis of Compound D-1 and Compound D-2) Compound D-1 and Compound D-2 were synthesized according to the following reaction.

[0234] [ka]

[0235] Into a four-neck flask purged with argon, bis(4-bromophenyl)bis(4-hexylphenyl)silane (20.0 g), 4'-propyl-[1,1'-biphenyl]-4-amine (15.9 g), tris(dibenzylideneacetone)dipalladium (Pd 2 (dba) 3 ) (0.552 g), 1,1'-bis(diphenylphosphino)ferrocene (DPPF) (0.669 g), sodium tert-butoxide (t-BuONa) (5.83 g), and toluene (200 mL) were added and heated at 95°C for 2 hours. The mixture was allowed to cool to room temperature, and insoluble matter was filtered off using Celite. The solvent was removed from the filtrate under reduced pressure, and the mixture was purified by column chromatography to obtain compound D-1 (22.8 g).

[0236] In a four-neck flask purged with argon, compound D-1 (20.0 g), 4-bromo -1- Iodobenzene (15.2 g), tris(dibenzylideneacetone)dipalladium (Pd 2 (dba) 3 ) (0.396 g), 1,1'-bis(diphenylphosphino)ferrocene (DPPF) (0.480 g), sodium tert-butoxide (t-BuONa) (4.16 g), and xylene (200 mL) were added and heated at 120°C for 2 hours. The mixture was allowed to cool to room temperature, and insoluble matter was filtered off using Celite. The solvent was removed from the filtrate under reduced pressure, and the mixture was purified by column chromatography to obtain compound D-2 (20.5 g).

[0237] Synthesis Example 5 (Synthesis of Compound E-1 and Compound E-2) Compounds E-1 and E-2 were synthesized according to the following reactions.

[0238] [ka]

[0239] Under an argon atmosphere, 1,4-dibromo-2,5-dihexylbenzene (20.0 g), 4-chlorophenylboronic acid (23.2 g), tetrakis(triphenylphosphine)palladium (Pd(PPh 3 ) 4 )(2.85g), Sodium Carbonate (Na 2 CO 3 ) (52.4 g), toluene (500 mL), ethanol (250 mL), and water (125 mL) were added to a four-neck flask and stirred at 100 ° C for 15 hours. The reaction solution was cooled to room temperature, and the organic layer was separated. In addition, the aqueous layer was extracted with toluene (100 mL × 3), combined with the organic layer, washed with water (100 mL × 3), and filtered using Celite and silica gel. The solvent was distilled off under reduced pressure, toluene (100 mL) and activated clay (10 g) were added, refluxed for 30 minutes, and filtered using Celite. This operation was repeated twice. The solvent was distilled off under reduced pressure, and ethanol (50 mL) was added to the obtained solid, and refluxed for 30 minutes. The solid was filtered and dried in vacuum to obtain monomer E-1 (18.5 g).

[0240] Under an argon atmosphere, the compound E-1 (15.0 g) obtained above, 4,4,4',4',5,5,5',5'-octamethyl-2,2'-bi-1,3,2-dioxaborolane (22.5 g), tris(dibenzylideneacetone)dipalladium (Pd 2 (dba) 3 ) (1.46 g), 2-dicyclohexylphosphino-2',4',6'-triisopropylbiphenyl (2.29 g), potassium acetate (AcOK) (18.9 g), and 1,4-dioxane (320 mL) were placed in a four-neck flask and heated at 100°C for 3 hours. The reaction solution was cooled to room temperature, the solvent was removed by distillation under reduced pressure, and the mixture was filtered using toluene (300 mL) and Celite. Activated carbon (10 g) was added to the filtrate, and the mixture was refluxed for 30 minutes twice. The solvent was removed by distillation under reduced pressure, and the obtained solid was repeatedly recrystallized using a hexane / ethanol mixed solvent and dried in vacuum. As a result, compound E-2 [2,2'-(2,5-dihexyl-[1,1':4',1"-terphenyl]4,4"-diyl)bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane)] (19.5 g) was obtained.

[0241] Synthesis Example 6 (Synthesis of Compound F-1 and Compound F-2) Compounds F-1 and F-2 were synthesized according to the following reactions.

[0242] [ka]

[0243] Into a four-neck flask purged with argon, bis(4-bromophenyl)-bis(4-hexylphenyl)silane (6.6 g), 4-aminobiphenyl (4.5 g), tris(dibenzylideneacetone)dipalladium (Pd 2 (dba) 3 ) (0.183 g), 1,1'-bis(diphenylphosphino)ferrocene (DPPF) (0.222 g), sodium tert-butoxide (t-BuONa) (1.92 g), and toluene (120 mL) were added and heated at 95°C for 7 hours. The mixture was allowed to cool to room temperature, and insoluble matter was filtered off using Celite. The solvent was removed from the filtrate under reduced pressure, and the mixture was purified by column chromatography to obtain monomer F-1 (6.0 g).

[0244] Into a four-neck flask purged with argon, compound F-1 (5.5 g) obtained above, 1-bromo-4-iodo-benzene (5.5 g), tris(dibenzylideneacetone)dipalladium (Pd 2 (dba) 3 ) (0.300 g), 1,1'-bis(diphenylphosphino)ferrocene (DPPF) (0.73 g), sodium tert-butoxide (t-BuONa) (1.9 g), and xylene (60 mL) were added and heated at 105°C for 7 hours. The mixture was allowed to cool to room temperature, and insoluble matter was filtered off using Celite. The solvent was removed from the filtrate under reduced pressure, and the mixture was purified by column chromatography to obtain compound F-2 (6.9 g).

[0245] Synthesis Example 7 (Synthesis of compound G-1) Compound G-1 was synthesized according to the following reaction.

[0246] [ka]

[0247] In an argon atmosphere, 1,4-dihexyl-2,5-dibromobenzene (8.08 g, 20.0 mmol), bis(pinacolatoyl) ) Jibolo hmm( 4,4,4',4',5,5,5',5'-Octamethyl-2,2'-bi-1,3,2-dioxaborolane) (12.19 g, 48.0 mmol), [1,1'-Bis(diphenylphosphino)ferrocene]palladium(II) dichloride (PdCl 2 (dppf) (0.98 g, 1.2 mmol), potassium acetate (KOAc) (11.78 g, 120.0 mmol), and dioxane (100 ml) were added and mixed, and then stirred under heating and reflux for 6 hours. Next, toluene and water were added, and the mixture was separated and washed with water. Next, sodium sulfate and activated carbon were added, and the mixture was stirred and then filtered through Celite (registered trademark). Next, the filtrate was concentrated to obtain a crude product (11.94 g). Next, the crude product was recrystallized with hexane and then washed with methanol. The obtained crystals were dried under reduced pressure to obtain compound G-1 (4.23 g). The structure of the obtained compound G-1 was confirmed by a nuclear magnetic resonance spectrometry ( 1 The identity was determined by H-NMR.

[0248] Synthesis Example 8 (Synthesis of Compound H-1 and Compound H-2) Compound H-1 and Compound H-2 were synthesized according to the following reactions.

[0249] [ka]

[0250] In a reaction vessel under an argon atmosphere, 2-amino-N-[(1,1'-biphenyl)-4-yl]-N-(4-bromophenyl)-9,9-dimethylfluorene (15.00 g, 29.04 mmol), 3-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)carbazole (7.66 g, 26.14 mmol), bis(triphenylphosphine)palladium(II) dichloride (Pd(PPh 3 ) 2 Cl 2 ) (0.41g, 0.58mmol), sodium carbonate (Na 2 CO 3 ) (7.70 g, 72.61 mmol), dioxane (290 ml), and water (145 ml) were added and mixed. The mixture was then stirred at 85° C. for 4 hours, and after the reaction was completed, the reaction mixture was allowed to cool to room temperature. The reaction mixture was then filtered using Celite (registered trademark) to remove impurities. The solvent was then distilled off from the filtrate, which was then purified by column chromatography to obtain compound H-1 (12.7 g). The structure of the obtained compound H-1 was confirmed by nuclear magnetic resonance ( 1 The identity was determined by H-NMR.

[0251] In an argon atmosphere, compound H-1 (7.00 g, 11.6 mmol), 1,3-dibromo-5-iodobenzene (4.62 g, 12.77 mmol), copper (I) iodide (CuI) (0.11 g, 0.58 mmol), trans-1,2-cyclohexanediamine (0.29 g, 2.55 mmol), sodium tert-butoxide (t-BuONa) (2.23 g, 23.23 mmol), and dioxane (35 ml) were added to a reaction vessel and mixed. Next, the mixture was stirred at 90° C. for 6 hours, and after the reaction was completed, the reaction mixture was allowed to cool to room temperature. Next, the reaction mixture was filtered using Celite (registered trademark) to filter out impurities. Next, the solvent was distilled off from the filtrate, and the filtrate was purified by column chromatography to obtain compound H-2 (6 g). The structure of the obtained compound H-2 was confirmed by a nuclear magnetic resonance spectroscope ( 1 The identity was determined by H-NMR.

[0252] Synthesis Example 9 Under an argon atmosphere, compound G-1 (2.61 g) synthesized in Synthesis Example 7 above, compound H-2 (4.39 g) synthesized in Synthesis Example 8 above, palladium acetate (11.8 mg), tris(2-methoxyphenyl)phosphine (111 mg), toluene (70 mL), and 20% by mass tetraethylammonium hydroxide aqueous solution (27.0 g) were added, and the mixture was heated under reflux for 6 hours. Next, phenylboronic acid (63.6 g), tetrakis(triphenylphosphine)palladium (121 mg), and 20% by mass tetraethylammonium hydroxide aqueous solution (27.0 g) were added, and the mixture was heated under reflux for 7 hours. Next, the aqueous layer was removed from the reaction mixture, and sodium N,N-diethyldithiocarbamate trihydrate (17.7 g) and ion-exchanged water (70 mL) were added, and the mixture was stirred at 85° C. for 6 hours. Next, the reaction mixture was separated into an organic layer and an aqueous layer, and the organic layer was washed successively with water, a 3% by mass aqueous solution of acetic acid, and water. Next, the organic layer was dropped into methanol to cause precipitation, filtered, and then dried to obtain a crude product. Next, the crude product was dissolved in toluene and purified using a column chromatograph filled with silica gel / alumina, and the solvent was distilled off under reduced pressure. Next, the obtained liquid was dropped into methanol to cause precipitation, filtered, and then dried to obtain polymer compound P-9 (3.24 g). The number average molecular weight (Mn) and dispersity (Mw / Mn) of the obtained polymer compound P-9 were measured by SEC. As a result, the number average molecular weight (Mn) and Mw / Mn of the polymer compound P-9 were 95,900 and 4.77, respectively.

[0253] The polymer compound P-9 thus obtained is presumed to be a polymer compound having the following structural units based on the monomer charging ratio.

[0254] [ka]

[0255] Example 1 Under an argon atmosphere, compound A-2 (2.13 g) synthesized in Synthesis Example 1 above, 2,2'-(2,5-dihexyl-1,4-phenylene)bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane) (compound G-1 synthesized in Synthesis Example 7) (0.837 g), palladium acetate (3.9 mg), tris(2-methoxyphenyl)phosphine (37.0 mg), toluene (60 mL), and 20% by mass tetraethylammonium hydroxide aqueous solution (9.03 g) were added to a four-neck flask and stirred at 85° C. for 6 hours. Next, phenylboronic acid (24.2 mg), tetrakis(triphenylphosphine)palladium(0) (40.5 mg), and 20% by mass tetraethylammonium hydroxide aqueous solution (9.03 g) were added and stirred for 3 hours. Then, sodium N,N-diethyldithiocarbamate trihydrate (5.92 g) dissolved in ion-exchanged water (50 mL) was added and stirred at 85° C. for 2 hours. After separating the organic layer from the water layer, the organic layer was washed with water, a 3% by mass aqueous acetic acid solution, and water. The organic layer was passed through a column chromatography filled with silica gel / alumina, and the solvent was distilled off under reduced pressure. The obtained liquid was dropped into methanol, and the precipitated solid was dissolved in toluene. Next, this solution was dropped into methanol to precipitate, and the precipitated solid was filtered and dried to obtain polymer compound P-1 (1.19 g). The number average molecular weight (Mn) and dispersity (Mw / Mn) of the obtained polymer compound P-1 were measured by SEC. As a result, (Mn) and Mw / Mn of the polymer compound P-1 were 106,000 and 1.94, respectively.

[0256] The polymer compound P-1 thus obtained is presumed to be a polymer compound having the following structural units based on the monomer charging ratio.

[0257] [ka]

[0258] Example 2 Under an argon atmosphere, compound B-1 (2.13 g) synthesized in Synthesis Example 2 above, 2,2'-(2,5-dihexyl-1,4-phenylene)bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane) (compound G-1 synthesized in Synthesis Example 7) (0.999 g), palladium acetate (2.1 mg), tris(2-methoxyphenyl)phosphine (20.2 mg), toluene (60 mL), and 20% by mass tetraethylammonium hydroxide aqueous solution (7.61 g) were added to a four-neck flask and stirred at 85° C. for 6 hours. Next, phenylboronic acid (23.3 mg), tetrakis(triphenylphosphine)palladium(0) (13.4 mg), and 20% by mass tetraethylammonium hydroxide aqueous solution (7.61 g) were added and stirred for 3 hours. Then, sodium N,N-diethyldithiocarbamate trihydrate (5.40 g) dissolved in ion-exchanged water (50 mL) was added, and the mixture was stirred at 85° C. for 2 hours. After separating the organic layer from the aqueous layer, the organic layer was washed with water, a 3% by mass aqueous solution of acetic acid, and water. The organic layer was passed through a column chromatography filled with silica gel / alumina, and the solvent was distilled off under reduced pressure. The obtained liquid was dropped into methanol, and the precipitated solid was dissolved in toluene. Next, this solution was dropped into methanol to precipitate, and the precipitated solid was filtered and dried to obtain polymer compound P-2 (1.19 g). The number average molecular weight (Mn) and dispersity (Mw / Mn) of the obtained polymer compound P-2 were measured by SEC. As a result, (Mn) and Mw / Mn of the polymer compound P-2 were 121,000 and 1.60, respectively.

[0259] The polymer compound P-2 thus obtained is presumed to be a polymer compound having the following structural units based on the monomer charging ratio.

[0260] [ka]

[0261] Example 3 Under an argon atmosphere, compound A-1 (1.88 g) synthesized in Synthesis Example 1 above, 4,4'-dibromobiphenyl (0.623 g), tris(dibenzylideneacetone)dipalladium (41.8 mg), tri-t-butoxyphosphine (13.2 mg), and toluene (20 mL) were added to a four-neck flask and stirred at 65 ° C. for 6 hours. Next, 4-bromobiphenyl (46.3 mg) was added and stirred for 3 hours. Then, sodium N,N-diethyldithiocarbamate trihydrate (6.81 g) dissolved in ion-exchanged water (50 mL) was added and stirred at 85 ° C. for 2 hours. After separating the organic layer from the water layer, the organic layer was washed with water, a 3 mass% aqueous acetic acid solution, and water. The organic layer was passed through a column chromatography filled with silica gel / alumina, and the solvent was distilled off under reduced pressure. The obtained liquid was dropped into methanol, and the precipitated solid was dissolved in toluene. Next, this solution was dropped into methanol to precipitate, and the precipitated solid was filtered and dried to obtain polymer compound P-3 (1.66 g). The number average molecular weight (Mn) and dispersity (Mw / Mn) of the obtained polymer compound P-3 were measured by SEC. As a result, (Mn) and Mw / Mn of the polymer compound P-3 were 89,000 and 1.89, respectively.

[0262] The polymer compound P-3 thus obtained is presumed to be a polymer compound having the following structural units based on the monomer charging ratio.

[0263] [ka]

[0264] Example 4 Under an argon atmosphere, compound B-1 (2.37 g) synthesized in Synthesis Example 2 above, 4,4'-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)biphenyl (0.902 g), palladium acetate (5.0 mg), tris(2-methoxyphenyl)phosphine (47.1 mg), toluene (65 mL), and 20% by mass tetraethylammonium hydroxide aqueous solution (11.4 g) were added to a four-neck flask and stirred at 85 ° C for 6 hours. Next, phenylboronic acid (24.2 mg), tetrakis(triphenylphosphine)palladium(0) (31.3 g), and 20% by mass tetraethylammonium hydroxide aqueous solution (11.4 g) were added and stirred for 3 hours. Then, sodium N,N-diethyldithiocarbamate trihydrate (5.40 g) dissolved in ion-exchanged water (50 mL) was added and stirred at 85 ° C for 2 hours. After separating the organic layer from the water layer, the organic layer was washed with water, a 3% by mass aqueous solution of acetic acid, and water. The organic layer was passed through a column chromatography packed with silica gel / alumina, and the solvent was distilled off under reduced pressure. The resulting liquid was dropped into methanol, and the precipitated solid was dissolved in toluene. Next, this solution was dropped into methanol to cause precipitation, and the precipitated solid was filtered and dried to obtain polymer compound P-4 (0.78 g). The number average molecular weight (Mn) and dispersity (Mw / Mn) of the obtained polymer compound P-4 were measured by SEC. As a result, (Mn) and Mw / Mn of the polymer compound P-4 were 11,000 and 2.45, respectively.

[0265] The polymer compound P-4 thus obtained is presumed to be a polymer compound having the following structural units based on the monomer charging ratio.

[0266] [ka]

[0267] Example 5 The procedure was the same as in Example 2, except that instead of compound B-1, compound C-1 synthesized in the above Synthesis Example 3 was used, and polymer compound P-5 (0.78 g) was obtained. The number average molecular weight (Mn) and dispersity (Mw / Mn) of the obtained polymer compound P-5 were measured by SEC. As a result, (Mn) and Mw / Mn of polymer compound P-5 were 73,000 and 3.70, respectively.

[0268] The polymer compound P-5 thus obtained is presumed to be a polymer compound having the following structural units based on the monomer charging ratio.

[0269] [ka]

[0270] Example 6 Under an argon atmosphere, compound D-2 (2.06 g) synthesized in Synthesis Example 4 above, 2,2'-(2,5-dihexyl-1,4-phenylene)bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane) (compound G-1 synthesized in Synthesis Example 7) (0.662 g), palladium acetate (3.7 mg), tris(2-methoxyphenyl)phosphine (34.6 mg), toluene (45 mL), and 20% by mass tetraethylammonium hydroxide aqueous solution (8.44 g) were added to a four-neck flask and stirred at 85° C. for 6 hours. Next, phenylboronic acid (24.2 mg), tetrakis(triphenylphosphine)palladium(0) (37.9 mg), and 20% by mass tetraethylammonium hydroxide aqueous solution (8.44 g) were added and stirred for 3 hours. Then, sodium N,N-diethyldithiocarbamate trihydrate (5.53 g) dissolved in ion-exchanged water (20 mL) was added and stirred at 85° C. for 2 hours. After separating the organic layer from the aqueous layer, the organic layer was washed with water, a 3% by mass aqueous acetic acid solution, and water. The organic layer was passed through a column chromatography filled with silica gel / alumina, and the solvent was distilled off under reduced pressure. The obtained liquid was dropped into methanol, and the precipitated solid was dissolved in toluene. Next, this solution was dropped into methanol to precipitate, and the precipitated solid was filtered and dried to obtain polymer compound P-6 (1.44 g). The number average molecular weight (Mn) and dispersity (Mw / Mn) of the obtained polymer compound P-6 were measured by SEC. As a result, the average molecular weight (Mn) and Mw / Mn of polymer compound P-6 were 58,000 and 1.52, respectively.

[0271] The polymer compound P-6 thus obtained is presumed to be a polymer compound having the following structural units based on the monomer charging ratio.

[0272] [ka]

[0273] Example 7 Under an argon atmosphere, compound D-2 (1.67 g) synthesized in Synthesis Example 4 above, compound E-2 [2,2'-(2,5-dihexyl-[1,1':4',1"-terphenyl]4,4"-diyl)bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane)] (0.887 g) synthesized in Synthesis Example 5 above, palladium acetate (3.1 mg), tris(2-methoxyphenyl)phosphine (28.8 mg), toluene (50 mL), and 20% by mass tetraethylammonium hydroxide aqueous solution (7.61 g) were added to a four-neck flask, and stirred at 85°C for 6 hours. Next, phenylboronic acid (24.2 mg), tetrakis(triphenylphosphine)palladium(0) (31.5 mg), and 20% by mass tetraethylammonium hydroxide aqueous solution (7.03 g) were added, and stirred for 3 hours. Then, sodium N,N-diethyldithiocarbamate trihydrate (4.67 g) dissolved in ion-exchanged water (20 mL) was added, and the mixture was stirred at 85° C. for 2 hours. After separating the organic layer from the aqueous layer, the organic layer was washed with water, a 3% by mass aqueous solution of acetic acid, and water. The organic layer was passed through a column chromatography filled with silica gel / alumina, and the solvent was distilled off under reduced pressure. The resulting liquid was dropped into methanol, and the precipitated solid was dissolved in toluene. Next, this solution was dropped into methanol to precipitate, and the precipitated solid was filtered and dried to obtain polymer compound P-7 (1.36 g). The number average molecular weight (Mn) and dispersity (Mw / Mn) of the obtained polymer compound P-7 were measured by SEC. As a result, (Mn) and Mw / Mn of the polymer compound P-7 were 47,000 and 2.80, respectively.

[0274] The polymer compound P-7 thus obtained is presumed to be a polymer compound having the following structural units based on the monomer charge ratio.

[0275] [ka]

[0276] Example 8 A glass substrate with indium tin oxide (ITO) patterned to a thickness of 150 nm was used as the first electrode (anode). This glass substrate with ITO was washed sequentially with a neutral detergent, deionized water, water, and isopropyl alcohol, and then subjected to UV-ozone treatment. Next, poly(3,4-ethylenedioxythiophene) / poly(4-styrenesulfonate) (PEDOT / PSS) (Sigma-Aldrich) was applied to the glass substrate with ITO by spin coating so that the dry thickness was 30 nm, and then dried. As a result, a hole injection layer with a thickness (dry thickness) of 30 nm was formed on the glass substrate with ITO.

[0277] A 1.0% by mass toluene solution of the polymer compound P-1 (hole transport material) of Example 1 was applied onto the hole injection layer by spin coating so as to give a dry film thickness of 30 nm, and then heat-treated at 230° C. for 60 minutes to form a hole transport layer. As a result, a hole transport layer having a thickness (dry film thickness) of 30 nm was formed on the hole injection layer.

[0278] In cyclohexane, the following structure:

[0279] [ka]

[0280] A quantum dot dispersion liquid was prepared by dispersing blue quantum dots of ZnTeSe / ZnSe / ZnS (core / shell / shell; average diameter = about 10 nm) having the above structure to a concentration of 1.0 mass %. The hole transport layer (particularly the polymer compound P-1) does not dissolve in cyclohexane. This quantum dot dispersion liquid was applied to the hole transport layer by spin coating so that the dry film thickness was 30 nm, and then dried. As a result, a quantum dot light-emitting layer having a thickness (dry film thickness) of 30 nm was formed on the hole transport layer. The light emitted by irradiating the quantum dot dispersion liquid with ultraviolet light had a central wavelength of 462 nm and a half-width of 30 nm.

[0281] This quantum dot light-emitting layer was completely dried. On this quantum dot light-emitting layer, lithium quinolate (Liq) and 1,3,5-tris(N-phenylbenzimidazol-2-yl)benzene (TPBI) (Sigma-Aldrich) as an electron transport material were co-deposited using a vacuum deposition apparatus. As a result, an electron transport layer with a thickness of 36 nm was formed on the quantum dot light-emitting layer.

[0282] Using a vacuum deposition apparatus, (8-quinolinolato)lithium (lithium quinolate) (Liq) was deposited on the electron transport layer, resulting in the formation of an electron injection layer having a thickness of 0.5 nm on the electron transport layer.

[0283] Aluminum (Al) was evaporated onto the electron injection layer using a vacuum evaporation apparatus. As a result, a second electrode (cathode) having a thickness of 100 nm was formed on the electron injection layer. This resulted in the quantum dot electroluminescence device 1 being obtained.

[0284] Example 9 A quantum dot electroluminescence device 2 was produced in the same manner as in Example 8, except that the polymer compound P-2 of Example 2 was used instead of the polymer compound P-1 in Example 8.

[0285] Example 10 A quantum dot electroluminescence device 3 was produced in the same manner as in Example 8, except that the polymer compound P-3 of Example 3 was used instead of the polymer compound P-1 in Example 8.

[0286] Example 11 A quantum dot electroluminescence device 4 was produced in the same manner as in Example 8, except that the polymer compound P-4 of Example 4 was used instead of the polymer compound P-1 in Example 8.

[0287] Example 12 A quantum dot electroluminescence device 5 was produced in the same manner as in Example 8, except that the polymer compound P-5 of Example 5 was used instead of the polymer compound P-1 in Example 8.

[0288] Example 13 A quantum dot electroluminescence device 6 was produced in the same manner as in Example 8, except that the polymer compound P-6 of Example 6 was used instead of the polymer compound P-1.

[0289] Example 14 A quantum dot electroluminescence device 7 was produced in the same manner as in Example 8, except that the polymer compound P-7 of Example 7 was used instead of the polymer compound P-1.

[0290] Comparative Example 1 In Example 8, instead of the polymer compound P-1, poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine) ) A comparative quantum dot electroluminescence device 1 was produced in the same manner as in Example 8, except that TFB (manufactured by Luminescence Technology Corp.) was used. The number average molecular weight (Mn) and dispersity (Mw / Mn) of TFB were measured by SEC. As a result, the (Mn) and Mw / Mn of TFB were 359,000 and 3.4, respectively.

[0291] [ka]

[0292] [Evaluation of quantum dot electroluminescence devices 1] The quantum dot electroluminescent devices 1 to 4 produced in Examples 8 to 11 and the comparative quantum dot electroluminescent device 1 produced in Comparative Example 1 were evaluated for luminous efficiency by the following method.

[0293] When a voltage is applied to each quantum dot electroluminescence element using a DC constant voltage power supply (Keyence, source meter), a current begins to flow at a constant voltage, and the quantum dot electroluminescence element emits light. 2 The voltage at this point is defined as the driving voltage (Vop) [V]. The light emission of each element is measured using a luminance measuring device (SR-3, manufactured by Topcom), and the current is gradually increased until the luminance reaches 100 nit (cd / m 2 ), the current is made constant and left as is. The current value (current density) per unit area is calculated from the area of ​​each element, and the luminance (cd / m 2 ) to current density (A / m 2 ) to calculate the current efficiency (cd / A). Note that the current efficiency indicates the efficiency of converting current into light emission energy (conversion efficiency), and the higher the current efficiency, the higher the performance of the element.

[0294] In addition, the external quantum efficiency (EQE) (%) at a luminance of 100 nit is calculated from the spectral radiance spectrum measured by the luminance measuring device, assuming Lambertian radiation, and the luminous efficiency is evaluated.

[0295] The results are shown in Table 1 below.

[0296] [Table 1]

[0297] The results in Table 1 above show that the quantum dot electroluminescent devices 1 to 7 of the examples can exhibit higher performance (current efficiency, external quantum efficiency) at a lower driving voltage than the comparative quantum dot electroluminescent device 1, which does not use the silicon-containing arylamine polymer of the present invention.

[0298] Example 15 In an argon atmosphere, compound F-2 (1.182 g) synthesized in Synthesis Example 6 above, 2,2'-(2,5-dihexyl-1,4-phenylene)bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane) (compound G-1 synthesized in Synthesis Example 7) (0.502 g), palladium acetate (2.19 mg), tris(2-methoxyphenyl)phosphine (20.33 mg), toluene (30 mL), and 20% by mass tetraethylammonium hydroxide aqueous solution (7.61 g) were added to a four-neck flask and refluxed for 8 hours. Next, phenylboronic acid (23.3 mg), bis(triphenylphosphine)palladium(II) dichloride (13.4 mg), and 20% by mass tetraethylammonium hydroxide aqueous solution (7.61 g) were added, and the mixture was heated and refluxed for 7 hours. Thereafter, the aqueous layer was removed, and sodium N,N-diethyldithiocarbamate trihydrate (5.40 g) and ion-exchanged water (40 mL) were added, followed by stirring at 85° C. for 2 hours. After separating the organic layer from the aqueous layer, the organic layer was washed with water, a 3% by mass aqueous solution of acetic acid, and water. The organic layer was dropped into methanol to precipitate the polymer compound, which was then filtered and dried to obtain a solid. This solid was dissolved in toluene and passed through a column chromatography filled with silica gel / alumina, and the solvent was distilled off under reduced pressure. The resulting liquid was dropped into methanol, and the precipitated solid was filtered and dried to obtain polymer compound P-8 (0.91 g). The number average molecular weight (Mn) and dispersity (Mw / Mn) of the obtained polymer compound P-8 were measured by SEC. As a result, the number average molecular weight (Mn) and Mw / Mn of the polymer compound P-8 were 26,000 and 2.4, respectively.

[0299] The polymer compound P-8 thus obtained is presumed to be a polymer compound having the following structural units based on the monomer charging ratio.

[0300] [ka]

[0301] Example 16 A glass substrate with indium tin oxide (ITO) patterned to a thickness of 150 nm was used as the first electrode (anode). This glass substrate with ITO was washed sequentially with a neutral detergent, deionized water, water, and isopropyl alcohol, and then subjected to UV-ozone treatment. Next, poly(3,4-ethylenedioxythiophene) / poly(4-styrenesulfonate) (PEDOT / PSS) (Sigma-Aldrich) was applied to the glass substrate with ITO by spin coating so that the dry thickness was 30 nm, and then dried. As a result, a hole injection layer with a thickness (dry thickness) of 30 nm was formed on the glass substrate with ITO.

[0302] Onto this hole injection layer, a toluene solution containing 0.2 mass% of polymer compound P-3 (hole transport material) of Example 3 and 0.8 mass% of polymer compound P-9 (hole transport material) of Synthesis Example 9 was applied by spin coating to a dry film thickness of 30 nm, and then heat-treated at 230° C. for 60 minutes to form a hole transport layer. As a result, a hole transport layer having a thickness (dry film thickness) of 30 nm was formed on the hole injection layer.

[0303] In cyclohexane, the following structure:

[0304] [ka]

[0305] A quantum dot dispersion liquid was prepared by dispersing red quantum dots of InP / ZnSe / ZnS (core / shell / shell; average diameter = about 10 nm) having the above structure to a concentration of 1.0 mass %. The hole transport layer (particularly the polymer compounds P-3 and P-9) does not dissolve in cyclohexane. This quantum dot dispersion liquid was applied to the hole transport layer by spin coating so that the dry film thickness was 30 nm, and then dried. As a result, a quantum dot light-emitting layer having a thickness (dry film thickness) of 30 nm was formed on the hole transport layer. The light emitted by irradiating the quantum dot dispersion liquid with ultraviolet light had a central wavelength of 627 nm and a half-width of 35 nm.

[0306] This quantum dot light-emitting layer was completely dried. On this quantum dot light-emitting layer, lithium quinolate (Liq) and 1,3,5-tris(N-phenylbenzimidazol-2-yl)benzene (TPBI) (Sigma-Aldrich) as an electron transport material were co-deposited using a vacuum deposition apparatus. As a result, an electron transport layer with a thickness of 36 nm was formed on the quantum dot light-emitting layer.

[0307] Using a vacuum deposition apparatus, (8-quinolinolato)lithium (lithium quinolate) (Liq) was deposited on the electron transport layer, resulting in the formation of an electron injection layer having a thickness of 0.5 nm on the electron transport layer.

[0308] Aluminum (Al) was evaporated onto the electron injection layer using a vacuum evaporation apparatus. As a result, a second electrode (cathode) having a thickness of 100 nm was formed on the electron injection layer. This resulted in the quantum dot electroluminescence device 8 being obtained.

[0309] Example 17 A quantum dot electroluminescence device 9 was prepared in the same manner as in Example 16, except that the polymer compound P-5 of Example 5 was used instead of the polymer compound P-3 in Example 16.

[0310] Example 18 A quantum dot electroluminescence device 10 was produced in the same manner as in Example 16, except that the polymer compound P-8 of Example 15 was used instead of the polymer compound P-3 in Example 16.

[0311] Comparative Example 2 In Example 16, instead of the polymer compounds P-3 and P-9, poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine) )A comparative quantum dot electroluminescence device 2 was prepared in the same manner as in Example 16, except that TFB (manufactured by Luminescence Technology Corp.) was used. The number average molecular weight (Mn) and dispersity (Mw / Mn) of TFB were measured by SEC. As a result, the (Mn) and Mw / Mn of TFB were 359,000 and 3.4, respectively.

[0312] [ka]

[0313] [Evaluation of quantum dot electroluminescence devices 2] The quantum dot electroluminescent devices 8 to 10 prepared in Examples 16 to 18 and the comparative quantum dot electroluminescent device 2 prepared in Comparative Example 2 were evaluated for luminous efficiency and luminous lifetime by the following methods.

[0314] (Luminous efficiency) When a voltage is applied to each quantum dot electroluminescence element using a DC constant voltage power supply (Keyence, source meter), a current begins to flow at a constant voltage, and the quantum dot electroluminescence element emits light. 2 The voltage at this point is defined as the driving voltage (Vop) [V]. The light emission of each element is measured using a luminance measuring device (SR-3, manufactured by Topcom), and the current is gradually increased until the luminance reaches 100 nit (cd / m 2 ), the current is made constant and left as is. The current value (current density) per unit area is calculated from the area of ​​each element, and the luminance (cd / m 2 ) to current density (A / m 2 ) to calculate the current efficiency (cd / A). Note that the current efficiency indicates the efficiency of converting current into light emission energy (conversion efficiency), and the higher the current efficiency, the higher the performance of the element.

[0315] In addition, the external quantum efficiency (EQE) (%) at a luminance of 100 nit is calculated from the spectral radiance spectrum measured by the luminance measuring device, assuming Lambertian radiation, and the luminous efficiency is evaluated.

[0316] The results are shown in Table 2 below. In Table 2 below, the weight average molecular weight (Mn) and the dispersity (Mw / Mn) indicate the Mn and Mw / Mn of the polymer compounds P-3 (Example 16), P-5 (Example 17), and P-8 (Example 18), respectively.

[0317] (Light Emitting Life) A DC constant voltage power supply (Keyence Corporation, source meter) was used to apply a predetermined voltage to each EL element, causing each quantum dot electroluminescence element to emit light. While measuring the emission of the quantum dot electroluminescence element with a luminance measuring device (Topcon Corporation, SR-3), the current was gradually increased until the luminance reached 325 nit (cd / m 2 ), the current was made constant and the device was left alone. The luminance measured by the luminance measuring device gradually decreased, and the time it took for the luminance to reach 50% of the initial luminance was taken as "LT50 (hr)."

[0318] The results are shown in the following Table 2. In Table 2, the relative value of each element when the LT50 of comparative quantum dot electroluminescence element 2 was set to 1.0 is shown in parentheses after the LT50.

[0319] [Table 2]

[0320] From the results of Table 2 above, it can be seen that the quantum dot electroluminescent devices 8 to 10 of the embodiment can exhibit higher performance (current efficiency, external quantum efficiency) at a low driving voltage compared to the comparative quantum dot electroluminescent device 2 that does not use the silicon-containing arylamine polymer of the present invention. In addition, the quantum dot electroluminescent devices 8 to 10 of the embodiment have significantly improved LT50 compared to the comparative quantum dot electroluminescent device 2. From these results, it is considered that the luminance and luminescence life can be dramatically improved by using the quantum dot electroluminescent device of the present invention in which two types of polymer compounds are combined. In this example, the red quantum dot electroluminescent device was evaluated, and it is considered that the same results as above can be obtained in the blue quantum dot electroluminescent device, etc.

[0321] [Evaluation of the properties of each polymer compound] The HOMO level (eV), LUMO level (eV) and glass transition temperature (Tg) (°C) of the polymer compounds P-1 to P-9 of Examples 1 to 7 and 15 and Synthesis Example 9 were measured by the following method. The results are shown in Table 3 below.

[0322] (HOMO level measurement) Each polymer compound is dissolved in xylene to a concentration of 1% by mass to prepare a coating solution. The coating solution prepared above is used to form a film on a UV-cleaned glass substrate with ITO by spin coating at a rotation speed of 2000 rpm, and then the film is dried on a hot plate at 150°C for 30 minutes to prepare a sample for measurement. The HOMO level of the sample is measured using an atmospheric photoelectron spectrometer (AC-3, manufactured by Riken Keiki Co., Ltd.). At this time, the tangent intersection point of the rising edge is calculated from the measurement result and is taken as the HOMO level (eV). The HOMO level is usually a negative value.

[0323] (LUMO level measurement) Each polymer compound is dissolved in toluene to a concentration of 3.2% by mass to prepare a coating solution. The coating solution prepared above is used to form a film on a UV-cleaned glass substrate with ITO by spin coating at a rotation speed of 1600 rpm, and then dried on a hot plate at 250°C for 60 minutes to prepare a sample for measurement (film thickness: approximately 70 nm). The obtained sample is cooled to 77K (-196°C) and the photoluminescence (PL) spectrum is measured. The LUMO level (eV) is calculated from the peak value on the shortest wavelength side of the PL spectrum.

[0324] (Glass transition temperature (Tg)) Each polymer compound is measured using a differential scanning calorimeter (DSC) (Seiko Instruments Inc., product name: DSC6000) by heating the sample to 300°C at a heating rate of 10°C / min and holding it for 10 minutes, then cooling it to 25°C at a cooling rate of 10°C / min and holding it for 10 minutes, and then heating it to 300°C at a heating rate of 10°C / min. After the measurement, the sample is cooled to room temperature (25°C) at a rate of 10°C / min.

[0325] [Table 3-1]

[0326] [Table 3-2]

[0327] Although the present invention has been described above with reference to embodiments and examples, the present invention is not limited to the specific embodiments and examples, and various modifications and changes are possible within the scope of the invention described in the claims. [Explanation of symbols]

[0328] 100...Electroluminescence element (EL element), 110...substrate, 120...first electrode, 130...hole injection layer, 140...hole transport layer, 150...light-emitting layer, 160...electron transport layer, 170...electron injection layer, 180...Second electrode.

Claims

1. A silicon-containing arylamine polymer composed only of repeating units of a structural unit (A) represented by the following formula (1): 【Chemistry 1】 However, Ar 1 each independently represents a substituted or unsubstituted aromatic hydrocarbon group having 6 to 25 carbon atoms or a substituted or unsubstituted heterocyclic aromatic group having 12 to 25 carbon atoms; R 1 each independently represents a hydrogen atom, a linear or branched alkyl group having from 1 to 12 carbon atoms, a linear or branched alkenyl group having from 2 to 12 carbon atoms, a linear or branched alkynyl group having from 2 to 12 carbon atoms, a cycloalkyl group having from 3 to 12 carbon atoms, or a substituted or unsubstituted aromatic hydrocarbon group having from 6 to 25 carbon atoms, Ar 2 is a divalent group selected from the following group: 【Chemistry 2】 However, R 211 ~R 269 each independently represents a hydrogen atom, a linear or branched alkyl group having from 1 to 12 carbon atoms, or a substituted or unsubstituted aromatic hydrocarbon group having from 6 to 25 carbon atoms.

2. The Ar 1 The silicon-containing arylamine polymer of claim 1 , wherein each of the groups is independently a group selected from the group consisting of: 【Chemistry 3】 However, R 111 ~R 134 each independently represents a hydrogen atom, a linear or branched alkyl group having from 1 to 12 carbon atoms, or a substituted or unsubstituted aromatic hydrocarbon group having from 6 to 25 carbon atoms.

3. The silicon-containing arylamine polymer according to claim 1 or 2, wherein the structural unit (A) is selected from structural units represented by the following formulas (A-1) to (A-4): 【Chemistry 4】 In the above, Alkyl means unsubstituted or substituted with an alkyl group.

4. An electroluminescence device material comprising the silicon-containing arylamine polymer according to any one of claims 1 to 3.

5. A composition for producing an electroluminescent device, comprising two or more polymers, at least one of which is the silicon-containing arylamine polymer according to any one of claims 1 to 3.

6. The composition for manufacturing an electroluminescent device according to claim 5, wherein at least one polymer has a constitutional unit represented by the following formula (A): 【Chemistry 5】 In the above, X is selected from structural units represented by the following formulas (2-1) to (2-6): 【Chemistry 6】 In the above formulas (2-1) to (2-6), Ar 100 is a substituted or unsubstituted trivalent aromatic hydrocarbon group having 6 to 60 carbon atoms, or a substituted or unsubstituted trivalent aromatic heterocyclic group having 3 to 60 ring atoms; Ar 200 and Ar 300 each independently represent a substituted or unsubstituted monovalent aromatic hydrocarbon group having 6 to 60 carbon atoms, or a substituted or unsubstituted monovalent aromatic heterocyclic group having 3 to 60 ring atoms; L 1 and L 2 each independently represent a single bond, a substituted or unsubstituted divalent aromatic hydrocarbon group having from 6 to 60 carbon atoms, or a substituted or unsubstituted divalent aromatic heterocyclic group having from 3 to 60 ring atoms; Ar 400 is a substituted or unsubstituted monovalent aromatic hydrocarbon group having 6 to 60 carbon atoms, or a substituted or unsubstituted monovalent aromatic heterocyclic group having 3 to 60 ring atoms, Y is a substituted or unsubstituted divalent aromatic hydrocarbon group having 6 to 60 carbon atoms, or a substituted or unsubstituted divalent aromatic heterocyclic group having 3 to 60 ring atoms.

7. An electroluminescence element comprising a first electrode, a second electrode, and one or more organic films disposed between the first electrode and the second electrode, 7. An electroluminescence device, wherein at least one layer of the organic film comprises the silicon-containing arylamine polymer according to claim 1 or the composition for producing an electroluminescence device according to claim 5.

8. The electroluminescence device according to claim 7 , wherein the organic film containing the silicon-containing arylamine polymer is a hole transport layer or a hole injection layer.

9. 9. The electroluminescence device according to claim 7, wherein the organic film has a light-emitting layer containing semiconductor nanoparticles or an organometallic complex.

Citation Information

Patent Citations

  • Organic electroluminescence element material, manufacturing method therefor, organic electroluminescence element material composition, and organic electroluminescence element

    JP2006352069A

  • Electroluminescent polymer

    JP2007537311A

  • Quantum point light emitting element with multiple quantum point layer

    JP2010199067A

  • Organic electroluminescence element

    JP2017224836A

  • Organic electroluminescent device

    US20130277617A1